Genome-Wide Identification of DOG1 Domain Containing Proteins and Their Role in Moisture Deficit Stress Tolerance in Tomato - Hara Gopal Krishnajee; Senthil Kumar Avinash; Dayanandhi Elangovan; Malarvizhi Mathiazhagan; Avvaerahally Thammannagouda Sadashiva; Laxman Ramanna Hunashikatti; Kumudini Belur Satyan; Kundapura V. Ravishankar (Plant Molecular Biology Reporter, 2026)

Preclinical evaluation of route-dependent immune responses following repeated administration of a Klebsiella pneumoniae lytic phage cocktail in rats - Sonam Rastogi; Mayank Gangwar; Sudhir Kumar Singh; Alka Shukla; Digvijay Singh; Vandana Rastogi; Deepak Kumar; Pooja Sachdeva; Gopal Nath (Molecular Biology Reports, 2026)

Comparative gut microbiota profiling of obese and normal-weight indian adults using 16S rRNA sequencing - Ranjeet Kumar Vishwakarma; Priyanka Gautam; Minakshi Sahu; Gopal Nath; Bhupendra Singh Yadav (Molecular Biology Reports, 2026)

Genome-wide association study identifies significant SNPs for milk production and stature traits in Karan Fries cattle - Pritam Pal; Ishmeet Kumar; Manisha Choudhary; Amritanshu Upadhyay; Irusappan Ilayaraja; Anil Chitra; Lal Muansangi; Gopal Gowane; T. V. Raja; Anupama Mukherjee; Sabyasachi Mukherjee (Mammalian Genome, 2026)

Quality-by-Design Steered Development and Validation of Analytical Method for the Estimation of Etodolac: Integration of Monte Carlo Simulations and Green Analytical Principles - Akshay Kumar; Mohit Kumar; Pallavi Bassi; Balraj Saini; Narinderpal Kaur; Chander Parkash Dora; Gopal Thakur (Journal of Pharmaceutical Innovation, 2026)

Gendered resilience in India’s seaweed farming: Highlighting policy lessons from the COVID-19 pandemic for inclusive Blue economy framework - Sundaram Swathi Lekshmi Perumal; Radhakrishnan Kalidoss; Gopal Nikita; D. Divu; Mojjada Suresh Kumar; V.P. Vipin Kumar; George Saju; S. Surya; R. Narayanakumar; Kingsly Jose; V.A. Leslie; S.S. Arabindoo; et al. (Marine Policy, 2026)

Synthesis and characterization of gold nanoparticles (AuNPs) using Lentinus sajor-caju extract: A multifaceted approach to antibacterial, anticancer and photocatalytic degradation efficiency - Kumar Manimaran; Thammasak Rojviroon; Orawan Rojviroon; Ranjith Rajendran; Dede Heri Yuli Yanto; Gopal Venkatesh; Gayathri Segaran; Sumonman Niamlang (South African Journal of Botany, 2026)

Mimosa pudica Linn. - An important medicinal plant: Pharmacognostic evaluation, bioactive compound isolation, structural elucidation, and in silico analysis - Kousik Ghosh; Karthick Gopal; Lakshmanan Narayanan; Vamsee Krishna K․; Akansha Pandey; Aswathi Mohan P․; Siva Surya; Suseem S R; S. Chitra; Preeti Sharma; Ajay Kumar Meena (Next Research, 2026)

Identification and expression analysis of genes involved in biosynthesis of Vitamin C and E in Capsicum species - Meenakshi Dubey; Khushbu Islam; Abdul Rawoof; Neha Tiwari; Vandana Jaiswal; Ajay Kumar; Jai Gopal Sharma; Nirala Ramchiary (The Nucleus, 2026)

Comparative Responses of Ulva Intestinalis and Chlorella Sorokiniana to Sargassum Derived Biostimulant: Implications on Biomass and Pigment Enhancement - Karuna Kumari Radha; J. T. Mary Leema; Nambali Valsalan Vinithkumar; Dilip Kumar Jha; Gopal Dharani (Thalassas: An International Journal of Marine Sciences, 2026)

Lactobacillus Fermentum MCC2760 Mitigates Oxidized Oil-Induced Metabolic Dysfunction and Gut-liver axis Perturbations: A Two-Generation Study in rats - Vyshali Ramesh Keremane; Hamsavi Gopal Kamala; Krishna Komatwar; Sai Kumar Somashekher; Ramaprasad Ravichandra Talahalli (Probiotics and Antimicrobial Proteins, 2026)

Acid phosphatase-producing Bacillus spp. from Arabian Sea sediments as a halophilic biostimulant for sustainable agriculture - Roobamathi Senthilkumar; Greeshma Mani; Kumar Thalavai Sivasankarasubbiah; Nishanthika Thenmozhi Kulasekaran; Karpaga Raja Sundari Balachandran; Dharani Gopal (Biologia, 2026)

Integrated Transcriptomic and Small RNA Profiling Reveals Regulatory Networks Associated With Seed Protein Accumulation in Chickpea (Cicer arietinum L.) - Gopal Kalwan; Deshika Kohli; Yashwant Kumar Yadava; Sheel Yadav; Suruchi Khanna; Ila Joshi; MS Nimmy; S. V. Amitha Mithra; Biswajit Mondal; Shailesh Tripathi; Satvir Kaur Grewal; Kishor Gaikwad; et al. (Journal of Plant Growth Regulation, 2026)

Microplastic contamination in locally and industrially produced organic fertilizers: Implications for sustainable agriculture and risk mitigation - Mahfuz Ahmmed; Md Hasibuzzaman; Ismail M. Rahman; Sadia Sultana Mitu; Tapos Kumar Chakraborty; Gopal Chandra Ghosh (Chemosphere, 2026)

Integrated experimental, statistical, and ANN validation study on concrete deterioration under acid rain, carbonation, and chloride environments - Y. H. Sudeep; V. Vijaykumar; M. S. Ujawl; Christo George; S. Karthik; Rakesh Kumar; Gopal Bharamappa Bekkeri; Kiran K. Shetty (Innovative Infrastructure Solutions, 2026)
Concrete structures in coastal–industrial regions are simultaneously exposed to acid rain, carbonation, and chloride ingress; however, most durability studies investigate these mechanisms independently, limiting realistic service-life prediction. This study presents an integrated experimental, statistical, and artificial neural network (ANN)-based evaluation of M40-grade concrete subjected to synthetic acid rain, accelerated carbonation, and combined carbonation–chloride environments. Laboratory simulations were conducted for exposure durations of 20, 40, 60, and 80 h to replicate aggressive atmospheric conditions. Mechanical degradation was assessed through compressive and splitting tensile strength tests, while chemical deterioration was quantified using depth-wise pH profiling and carbonation depth measurements. Results revealed that compressive strength decreased by up to ~ 25% under acid rain exposure and showed greater deterioration under combined carbonation–chloride conditions. Splitting tensile strength exhibited higher sensitivity to degradation, with reductions exceeding 20% at prolonged exposure durations. Surface pH declined from 12.6 to approximately 8.8, confirming rapid alkalinity loss in the outer 1 cm zone. Carbonation depth increased progressively, reaching ~ 11.5 mm in the combined exposure environment. Regression analysis demonstrated strong inverse correlations (R 2 > 0.90) between carbonation depth and mechanical properties, while one-way ANOVA confirmed statistically significant differences across exposure durations ( p < 0.05). To enhance predictive capability, an ANN model was developed using experimental parameters as inputs, achieving high prediction accuracy (R 2 = 0.98 for training and R 2 = 0.96 for testing). The findings highlight synergistic deterioration effects of multi-environmental exposure and emphasize durability-based design strategies for reinforced concrete structures in aggressive environments.

Deep ocean bacterial metabolites improve host survival and modulate immune-associated responses in Caenorhabditis elegans during Pseudomonas pathogenesis - Bynedi Seshadhri Chinna Mounish; Arumugam Ganesh Kumar; Gopal Dharani; Toleti Subba Rao; Krishnaswamy Balamurugan (Archives of Microbiology, 2026)

Metagenomic mining of microbial communication genes from Indian deep-sea sediments using a quorum sensing- and quenching-related protein database - D. Kesavan; Ramu Meenatchi; Raja Mohanakrishna; Anita Tripathi; Yashwanth B.S; Saravanane Narayanane; Saurav Gupta; Pushplata Yadav; Mukesh Pasupuleti; Greeshma Mani; Karpaga Raja Sundari Balachandran; Vijaya Raghavan Rangamaran; et al. (Marine Genomics, 2026)

Functional characterization of post-transcriptional gene silencing suppressors and effects of mixed infection in okra enation leaf curl virus - Aparna Chodon; Nithyasree Selvakumar; Saravana Kumar Thavamani; Sneka Ramesh; Gopal Pandi (VirusDisease, 2026)

In Silico Analysis of Phospholipases Involved in Drought Stress in Lipid Signalling: A Genome-Wide Study in Saccharum Species - Palanivel Gopal Santhosh Kumar; Rachel Lissy Vargheese; Nandini Karthikeyan; Indusha Yazhini Sankararaj; Akila Dharshini Venkatachalam; Manimekalai Ramaswamy; Lakshmi Kasirajan (Sugar Tech, 2026)

Genotypic Adaptations and Mechanisms of Salinity Tolerance in Dragon Fruit (Selenicereus spp.) - Vijaysinha Dhanasingrao Kakade; Nishigandha Kokani; Amrut Sanjay Morade; Gopal Ramdas Mahajan; Sangram Bhanudas Chavan; Raj Kumar; Machindra Agale; Shubhada Tayade; Karnar Manjanna Boraiah; Dinesh Jinger; Gaurav Singh; Kotha Sammi Reddy (International Journal of Environmental Research, 2026)

Effect of Nano Iron Application on Growth and Yield Parameters of Nectarine in the Mid-Hill Region of Himachal Pradesh - Suresh Kumar; Manohar Lal Verma; Gopal Singh; Mukesh Kumar; Yashpal Singh Bisht (Applied Fruit Science, 2026)

Soil moisture estimation using Sentinel-1 SAR and field observation in the Eastern Ghats region of India - Uday Mandal; M. Madhu; Ramajayam Devarajan; Randhir Kumar; Gopal Kumar; HC Hombegowda; SK Samal; Saswat Kumar Kar; P. Raja; Pyla Sravani; Sitanshu Sekhar Patra (Environmental Monitoring and Assessment, 2026)

Gut Microbiome in Obesity: A Narrative Review of Mechanisms, Interventions, and Future Directions - Ranjeet Kumar Vishwakarma; Priyanka Gautam; Minakshi Sahu; Gopal Nath; Bhupendra Singh Yadav (Probiotics and Antimicrobial Proteins, 2026)

Radon-thoron exhalation rates in mineral-enriched beach sand of the Chennai coast, India - M. John Samson; K. Manikanda Bharath; A. Vidyasakar; K. Ajith Kumar; V. Arun Bharathi; Satyanarayan Bramha; S. Chandrasekaran; Kannaiyan Neelavannan; V. Gopal; S. Ajith Kumar; N. Sivakumar (Environmental Geochemistry and Health, 2026)

Microplastics in aquaculture ponds of Bangladesh: Source attribution, pollution load, and ecological risk assessment - Sarajit Sarker; Abu Rayhan; MD Jahid Hasan; Aditi Biswas; Sk Mahmudul Hasan Asif; Tapos Kumar Chakraborty; Samina Zaman; Gopal Chandra Ghosh; Monishanker Halder; Nazmul Hossain (Marine Pollution Bulletin, 2026)

Exploring the potential of tyre derived graphene for supercapacitor applications: A DFT approach - Rahul Kumar Jha; Anurag Srivastava; Nand Gopal Sahoo; Suman Mahendia; Sravendra Rana (Journal of Environmental Chemical Engineering, 2026)

Solid waste characterization and floristic assessment of municipal solid waste dumping zone in Almora district of Uttarakhand, western Himalaya - Parnika Gupta; Vasudha Agnihotri; Nanda Gopal Sahoo; Sunil Kumar Suman (Biomass and Bioenergy, 2026)

Atmospheric microplastics deposition in Dhaka City, Bangladesh: occurrence, distribution and ecological risk assessment - Md Tauhiduzzaman; Nishat Salsabil; Kobita Khatun; Md Muhaiminul Haque; Ahsan Habib; Mst Shamima Akter; Sojib Islam; Md Hasibuzzaman; Ismail M. Rahman; Mahfuz Ahmmed; Samina Zaman; Tapos Kumar Chakraborty; et al. (Atmospheric Pollution Research, 2026)

Spatio-Temporal Assessment of Groundwater Level Trends for Sustainable Management in the Coastal Region of India - Sujeet Desai; Bappa Das; Dikshita A. Shetkar; Gopal Mahajan; Basavareddy; Parveen Kumar (Water Conservation Science and Engineering, 2026)

Assessment of Groundwater and Surface Waterlogging in the Indira Gandhi Nahar Project (IGNP) Phase-I, India, Using Google Earth Engine - Survey Daman Sharma; Nitesh Patidar; Manmohan Kumar Goel; Anupma Sharma; Gopal Krishan; Surjeet Singh; Sumant Kumar (Journal of the Indian Society of Remote Sensing, 2026)

High throughput phenotyping techniques in accelerated plant breeding - Lakshmi Bhavani Lankada; G. Prasanna; Narkhede Gopal Wasudeo; Konusothu Subhasri; G. Harish Kumar; Mehdi Rahimi (Journal of Crop Science and Biotechnology, 2026)

Influence of Plant Growth Regulators on Growth, Yield and Fruit Quality of Strawberry Cv. ‘Camarosa’ Under Protected Conditions - Suman Bodh; Jitender Kumar Chauhan; Gopal Singh; Meera Devi; Divya Pandey (Applied Fruit Science, 2026)

Emissions and health risks of prolonged incense burning in worship spaces: simulated real-life scenarios and strategic approaches for exposure assessment, control, and mitigation - Gopal Ashok Gupta; Roshan Kumar Singh; Janakarajan Ramkumar; Sandip Patil; Tarun Gupta (Air Quality, Atmosphere & Health, 2026)

Microneedle-Assisted Delivery of Biologics: From Large Molecules to Cancer Vaccines - Salma Younas; Mohit Kumar; Ramsha Khalid; Kirthana Gopal; Akshay Kumar; Pornanong Aramwit; Syed Mahmood (AAPS PharmSciTech, 2026)

Source tracking, pollution load, and risk assessment of microplastics pollution in agricultural soils of Bangladesh using machine learning and multi-matrix approaches - Aditi Biswas; Partha Chandra Debnath; Khandakar Rashedul Islam; MD Jahid Hasan; Sarajit Sarker; Sk Mahmudul Hasan Asif; Md Abu Rayhan; Md Simoon Nice; Monishanker Halder; Tapos Kumar Chakraborty; Samina Zaman; Gopal Chandra Ghosh (Environmental Pollution, 2026)

Stability Indices, AMMI and GGE Biplots Analysis of Forage Oat Germplasm Under Variable Growing Regimes in the Northwestern Himalayas - Sanjay Kumar Sanadya; Vinod Kumar Sood; Sawan Kumar; Gaurav Sharma; Rhitisha Sood; Gopal Katna; Muluken Enyew; Smrutishree Sahoo (Agricultural Research, 2026)

Exploring genetic polymorphisms in five fecundity genes and their association with litter traits in Indian Beetal crossbred goats - Konangiyur Arthanari Saravanan; Rani Alex; Gopal Ramdasji Gowane; Sahana Varadanayakanahalli Narayanaswamy; Kashif Dawood Khan; Ashish Yadav; Shambhuraditya Chavan; Rinki Paul; Vikas Vohra; Arun Kumar (The Nucleus, 2026)

A hybrid deep learning based framework for prediction of rice yield through integration of biophysical parameters and optical remote sensing data in India - Rafath Samrin; Pundru Chandra Shaker Reddy; K. Arun Kumar; Natha Deepthi; C. Mithra; S Bhargavi Latha; Sucharitha Yadala; Gopal Kumar Thakur (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Integrated computational-experimental pipeline for CHK1 inhibitor discovery: structure-based identification of novel chemotypes with anticancer activity - Dhanushya Gopal; Manasa Pacharla; Nehal Arvind Kumar; Prem Kumar; Angelin Preetha Sathiyanathan; Jaikanth Chandrasekaran; Mohit Agrawal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Prediction of Urban Growth Using Cellular Automata (CA) Based Model: A Case of Bhopal City - Gopal Kumar; Supriya Vyas (Journal of the Indian Society of Remote Sensing, 2026)

Synergy between Piriformospora Indica and Salicylic Acid Modulates Maize Stress Physiology, Ultrastructure, and Gene Expression - Sunil K. Singh; Rakesh Pandey; Chanda Panwar; Pankaj Kumar; Sumit Sharma; Sonali Batra; Pradeep Kumar; Jai Gopal Sharma; Madhulika Singh; Bhoopander Giri (Journal of Plant Growth Regulation, 2026)

Correction to: Ursolic Acid Emulgel Augmented Drug Delivery in Leishmania donovani, A Causative Agent for Cutaneous Leishmaniasis: In Vitro Characterization and Anti-Amastigote Activity - Spandana Gollapalli; Soyal Sayyed; Soham Loharkar; Atul Mourya; Gopal Bajad; Shristi Arya; Dinesh Kumar Chandanapalli; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Poly(ε-Caprolactone) Microparticles of Andrographolide for Paracetamol-Induced Liver Iinjury: Box-Behnken Design Based Optimization, In Vitro and In Vivo Studies - Nitin Wadate; Pawan Devangan; Pankaj Kumar; Gopal Bajad; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Identification of novel signal of DRESS associated with antibiotics: a disproportionality analysis of the FDA adverse event reporting system (FAERS) database - Khushi Goyal; Ruchika Sharma; Ashok Kumar Datusalia; Gopal L. Khatik; Anoop Kumar (European Journal of Clinical Pharmacology, 2026)

Association of NLRP3 (rs10754558, rs3806268, rs12137901) and ABCG2 (rs2231142) Gene Polymorphisms in Gout Susceptibility Among Asian and Caucasian Populations: A Meta-Analysis - Sharon Benita Stephen; Niranjan Gopal; R. Muthuvel; S. Waheeda; Gowtham Kumar Subbaraj (Indian Journal of Clinical Biochemistry, 2026)

Opposition based learning for metaheuristic algorithms: Theory, variants, applications, and performance evaluation - Rebika Rai; Buddhadev Sasmal; Arunita Das; Totan Bharasa; Krishna Gopal Dhal; Prabir Kumar Naskar (Swarm and Evolutionary Computation, 2026)

Monsoon-driven biogeochemical shifts and acidification risk in tropical estuarine ecosystems: A case study from the Indian coast - Mukunda Kesari Khadanga; Rajani Kanta Mishra; Gopal Krushna Swain; Basanta Kumar Jena; Pratap Kumar Mohanty (Marine Environmental Research, 2026)

Tracing surface-adhered and internalized microplastics in leafy vegetables across urban and rural agroecosystems: Occurrence, characteristics, pollution indices, and exposure assessment - Ismail M. Rahman; Gopal Chandra Ghosh; Sadia Sultana Mitu; Mahfuz Ahmmed; Md Hasibuzzaman; Danisha Sultana; Jarin Tasnim Asha; Sojib Islam; Md. Tauhiduzzaman; Tapos Kumar Chakraborty; Samina Zaman; Seiya Hanamoto; et al. (Journal of Hazardous Materials, 2026)

Degraded land: Assessment, impact, restoration, and challenges - Gulshan Kumar Sharma; Dinesh Jinger; I. Rashmi; Manoj Kumar; Nandha Kumar Natrajan; Roomesh Kumar Jena; Raj Kumar; Suresh Kumar; Kavita Kumari; Rajesh Kaushal; Anupam Barh; Trisha Roy; et al. (Journal of Environmental Management, 2026)

Microplastic contaminants in eggs: Identification, characterization, and potential risks - Md Abu Rayhan; Partha Chandra Debnath; Gehendra Kharel; Khandakar Rashedul Islam; Sarajit Sarker; Aditi Biswas; MD Jahid Hasan; Sk Mahmudul Hasan Asif; Md Sozibur Rahman; Baytune Nahar Netema; Md Simoon Nice; Pragga Chowdhury; et al. (Food Bioscience, 2026)

Microbiota Dysbiosis in Amyotrophic Lateral Sclerosis: A Systematic Review of Human Studies - Priyanka Gautam; Ranjeet Kumar Vishwakarma; Manabesh Nath; Gopal Nath; Abhishek Pathak (Molecular Neurobiology, 2026)

Genome wide identification, characterization and evolutionary relationship analysis of the Dof gene family in Drumstick plant (Moringa oleifera) - Senthil Kumar Avinash; Malarvizhi Mathiazhagan; Dayanandhi Elangovan; Hara Gopal Krishnajee; Pooja Bharti; Raja Shankar; Laxman R. Hunashikatti; Kundapura V. Ravishankar (Genetic Resources and Crop Evolution, 2026)

Doomsday Clocks in the Anthropocene Era: Understanding Existential Risks To Humanity - Sudhanshu Kumar; Gopal Shankar Singh (Anthropocene Science, 2025)

Ensemble Learning Based Method for Contingency Classification and Ranking in a Large Power System - Dheeraj Kumar Dhaked; Deepak Kumar Goyal; V.L. Narayanan; Yatinda Gopal; Dinesh Birla (Next Research, 2025)

Assessment of Groundwater Quality Using Statistical and Hydro-Chemical Approaches: A Case Study of Mahoba District, India - Hemant Kumar Pandey; Vishal Kumar Singh; Sudhir Kumar Srivastava; Ram Pal Singh; Sanjay Gopal Bhartariya (Water, Air, & Soil Pollution, 2025)

Plant invasion in protected areas: case studies and insights from India - Megha Shruti; Sipu Kumar; Amit Kumar; Navendu Page; Gopal Singh Rawat (Tropical Ecology, 2025)

Dietary Lipid Levels and Bile Acid Supplementation: Effects on Growth, Metabolism and Fatty Acid Composition in Asian Seabass (Lates calcarifer) - Gopal Sanjay; Ishfaq Nazir Mir; Nathan Felix; Amit Ranjan; Chinakannu Sathish Kumar (Proceedings of the Zoological Society, 2025)

Harnessing Plant Bio-regulators and Bio-stimulant for Enhanced Vegetative Growth, Physiological Performance and Yield Efficiency of Oriental Persimmon (Diospyros Kaki L.) - Neha Thakur; Dharam Paul Sharma; Gopal Singh; Pardeep Kumar; Nitin Sharma (Journal of Soil Science and Plant Nutrition, 2025)

Ursolic Acid Emulgel Augmented Drug Delivery in Leishmania Donovani, A Causative Agent for Cutaneous Leishmaniasis: In Vitro Characterization and Anti-Amastigote Activity - Spandana Gollapalli; Soyal Sayyed; Soham Loharkar; Atul Mourya; Gopal Bajad; Shristi Arya; Dinesh Kumar Chandanapalli; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2025)

In-vitro analysis of biofilm formation and synergistic antibiotic-phage therapy for amoxicillin-resistant Escherichia coli - Ranjeet Kumar Vishwakarma; Bhupendra Singh Yadav; Priyanka Gautam; Minakshi Sahu; Ayu Singh; Ashish Kumar; Gopal Nath (Archives of Microbiology, 2025)

In‐Situ Diversification and Regional Attributes Shape Asymmetric Diversity of Miliusa (Annonaceae) in Tropical Asia - Abhishek Gopal; Navendu Page; Amit Kumar; Neha Tiwari; Velusamy Sundaresan; Jahnavi Joshi (Journal of Biogeography, 2025)
Aim We examine biogeography and speciation patterns in Miliusa Lesch. ex A. DC. (~65 species) distributed in tropical Asia to understand the uneven distribution of its extant diversity, with Indo‐Burma having twice the species richness of peninsular India (PI) and four times that of Wallacea and Sahul. Location Tropical Asia. Taxon Miliusa (Annonaceae). Methods Phylogenetic reconstruction was performed using six plastid markers across fifty‐two species using both ML and BI approaches. Divergence times were estimated using two fossil calibrations and an optimized relaxed clock, and ancestral areas were inferred with ‘BioGeoBEARS’. Speciation rates were examined using ClaDS and the DR statistic, and community structure was assessed using phylogenetic diversity metrics. Results Miliusa likely originated in the mid‐Miocene, with Indo‐Burma and PI as its ancestral range. Its extant diversity is primarily attributed to in‐situ speciation, with dispersal or vicariance playing limited but important roles in PI, and Wallacea and Sahul. Lineages in Indo‐Burma began accumulating in the mid‐Miocene, preceding those in PI (~10 Myr) and Wallacea and Sahul (~5 Myr). PI showed signs of saturation in lineage accumulation and had lower speciation rates compared to Wallacea and Sahul and Indo‐Burma, both of which had similar rates. All regions exhibited phylogenetic clustering, but Indo‐Burma and PI differed in their sensitivity to phylogenetic depths. Main Conclusions The uneven diversity of Miliusa is shaped by time for speciation, age and dispersal, although their relative influence varies across regions. In Indo‐Burma, long‐term geo‐climatic stability and greater niche availability likely facilitated the persistence of lineages, rapid speciation and dispersal, making it an evolutionary hotspot for Miliusa . In contrast, PI exhibited lower richness and speciation rates despite being old, likely due to the contraction of wet habitats in the Miocene that limited available niches for speciation. Lineages in Wallacea and Sahul show typical island‐like radiations, with speciation rates comparable to the larger and more geo‐climatically stable Indo‐Burma, despite their more recent origin. Overall, our results highlight the role of Miocene‐driven climatic vicariance and Pliocene–Pleistocene climatic fluctuations in shaping the diversification dynamics and regional diversity patterns across tropical Asia.

Physicochemical characterization, ecological risk assessment and spatial distribution of microplastics in Bangladesh's largest coral reef systems - Md Simoon Nice; Tapos Kumar Chakraborty; Gehendra Kharel; Baytune Nahar Netema; Khandakar Rashedul Islam; Pragga Chowdhury; Partha Chandra Debnath; Md Sozibur Rahman; Md Abu Rayhan; Samina Zaman; Gopal Chandra Ghosh (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Machine learning-powered geospatial mapping of groundwater quality and salinity: towards sustainable water management in Southern India - Saravana Kumar Maluventhi; Prabakaran Kulandaisamy; Muthuramalingam Rajendran; Dharshan Ragavendar Balagurumoorthi; Gopal Veeramalai (Stochastic Environmental Research and Risk Assessment, 2025)

Automatic detection of the number of aircraft over satellite data using deep learning - Jai Gopal Singla; Gautam Kumar Jaiswal; Renu Chaudhary; Darshan Kumar Patel (Journal of Earth System Science, 2025)

Emerging contaminants in urban Soils: Characterization, sources, and environmental impacts of microplastics in southern India - M. Bhuvaneswari; V. Gopal; R. Vinoth; R. Aakash; N.M. Swetha; S. Vinoth kumar; R.R. Krishnamurthy; M.Suresh Gandhi; Renuka Sharma; Ramamoorthy Ayyamperumal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Phosphate buffer saline as a dual-functional solvent: Enabling multiple cationic dye degradation and copper ion detection using silver nanospheres - Akash Kumar; Raja Gopal Rayavarapu (Journal of Environmental Chemical Engineering, 2025)

Metabasite from Greater Himalayan Crystalline sequence of Garhwal Himalayas: P-T evolution and implication for high-pressure metamorphism - Anubha Bhandari; Alok Kumar; Siladitya Sengupta; Joy Gopal Ghosh; Moumita Mitra Sinha (Journal of Asian Earth Sciences, 2025)

Harnessing a deep-sea EAL-domain enzyme for quorum quenching and biofilm control in food pipelines - Ramu Meenatchi; P. Snega Priya; Nitya Sunanda Appikatla; Raja Mohanakrishna; Damotharan Kesavan; J.T. Mary Leema; Sree Sankar Darveekaran Nair; Saurav Gupta; Pushplata Yadav; Saravanane Narayanane; Karpaga Raja Sundari Balachandran; Vijaya Raghavan Rangamaran; et al. (International Journal of Food Microbiology, 2025)

Unveiling the hidden pollutants in the indoor environment: Focus on microplastic pollution and its related risks in the educational institutions of megacity, Bangladesh - Tapos Kumar Chakraborty; Partha Chandra Debnath; Gehendra Kharel; Baytune Nahar Netema; Md Simoon Nice; Khandakar Rashedul Islam; Pragga Chowdhury; Md Sozibur Rahman; Samina Zaman; Gopal Chandra Ghosh; Monishanker Halder; Nazmul Hossain (Environmental Pollution, 2025)

Participatory nature-driven urbanism: a pathway to achieving SDG-11 through community-led action - Nazuk Bhasin; Sudhanshu Kumar; Gopal Shankar Singh (Urban Ecosystems, 2025)

Recent advancements in drug development for pulmonary tuberculosis - Koushik Mukherjee; Pritam Saha; Kirat Kumar Ganguly; Somjyoti Chakraborty; Swarnali Ghosh; Gopal Kundu (Archives of Microbiology, 2025)

Amino acid metabolism in cervical cancer: Mechanisms and implications in therapy - Roopak Murali; Sivapriya Singaraj; Isha Govindh; Pooja Singh; Sandhya Sundaram; Satish Srinivas; Gopal Gopisetty; Harish C. Chandramoorthy; Rajesh Kumar Gandhirajan (Next Research, 2025)

A potential interaction-based approach for appraising robustness and identifying critical links of regional road networks exposed to repeated flooding: case study of Dibrugarh district, Assam, India - Gopal Chandra Banik; Subrata Kumar Paul; Sudip Kumar Roy (Applied Geomatics, 2025)

Stauntonia grandiflora (Lardizabalaceae): an addition to Indian flora from Darjeeling-Sikkim Himalayas with its typification - Vinay Ranjan; Anant Kumar; Gopal Krishna (Vegetos, 2025)

Integrated AI and machine learning pipeline identifies novel WEE1 kinase inhibitors for targeted cancer therapy - Jaikanth Chandrasekaran; Dhanushya Gopal; Lokesh Vishwa Sureshkumar; Infant Xavier Santhiyagu; Varsha Senthil Kumar; Bhuvaneshwari Munuswamy; Beevi Fathima Harshatha Mohamed You Gani; Mohit Agrawal (Molecular Diversity, 2025)

Effective Use of Waste Basalt Rock Powder for Stabilizing Kasaoka Clay: Insights and Environmental Value - Gopal Kumar Pathak; Kimitoshi Hayano (Geotechnical and Geological Engineering, 2025)
This study evaluated the innovative use of basalt rock powder (BRP), a by-product of basalt mining, as an eco-friendly stabilizer for soft clay soils, with a particular focus on Kasaoka clay in Japan. The challenges associated with managing clay-rich surplus soils—such as poor engineering properties, high water retention, and disposal restrictions—were addressed by utilizing BRP in combination with blast furnace cement type B (BFCB) to form a hybrid stabilizer. Laboratory experiments were conducted to assess the geotechnical performance, environmental benefits, and scalability of the proposed stabilization approach. The results showed that BRP significantly improved the strength and compaction characteristics of Kasaoka clay. At a BRP content of 30%, the treated clay met embankment material standards, achieving a cone index ( q c ) greater than 800 kN/m 2 . Furthermore, the hybrid stabilizer combining BRP and BFCB demonstrated enhanced strength gains due to synergistic reactions. The maximum dry density ( ρ dmax ) increased from 1.51 g/cm 3 for untreated clay to 1.65 g/cm 3 for BRP-treated clay, with further optimization observed in the hybrid mixes Environmental analysis highlighted the potential for significant reductions in CO 2 emissions through the use of BRP. Compared with conventional stabilizers such as ordinary Portland cement, the hybrid stabilizer reduced CO 2 emissions by 59.3% without carbonation and by 78.1% when carbonation was considered. These findings underscore the sustainability benefits of the proposed method, aligning with global efforts to reduce the carbon footprint of construction materials. In conclusion, the study demonstrates that the BRP–BFCB hybrid stabilizer offers a promising solution for the sustainable reuse of industrial by-products in soil stabilization. It effectively addresses technical challenges while promoting resource efficiency and environmental sustainability. Future research is recommended to validate these results through field-scale studies and to explore the incorporation of additional waste materials to further enhance performance and cost-effectiveness.

Assessment of climate change vulnerability of agriculture in coastal districts of India using principal component analysis and entropy-based methods - Bappa Das; Sonam Sah; K. V. Reddy; S. J. Balaji; Sujeet Desai; Gopal Mahajan; Pooja Singh; Saurav Saha; Uthappa AR; Parveen Kumar; V. K. Sehgal; Ram N. Singh; et al. (Theoretical and Applied Climatology, 2025)

An innovative ensemble approach of deep learning models with soft computing techniques for GIS-based drought-zonation mapping in Rarh Region, West Bengal - Gopal Chowdhury; Sayantan Mandal; Ashis Kumar Saha (Environmental Science and Pollution Research, 2025)

Microplastics under siege: Biofilm-forming marine bacteria from the microplastisphere and their role in plastic degradation - Gajendra Joshi; Prasun Goswami; Dilip Kumar Jha; Nambali Valsalan Vinithkumar; Gopal Dharani (Science of The Total Environment, 2025)

Production of Phytase by Penicillium oxalicum in Solid State Fermentation Exhibiting Hydrolysis of Phytates and Haloperoxidase Activity - Priya; Bijender Singh; Ravi Kumar Goswami; Jai Gopal Sharma; Bhoopander Giri (Indian Journal of Microbiology, 2025)

Predictive Role of Serotonin Receptor (5HTR2A) and Dopamine Receptor (DRD2) gene polymorphisms in risperidone-induced weight gain and hyperprolactinemia in patients with schizophrenia - Alladi Charanraj Goud; Ravi Philip Rajkumar; Deepak Gopal Shewade; Luxitaa Goenka; Suresh Kumar Srinivasamurthy (European Journal of Clinical Pharmacology, 2025)

Estimation of heavy metals in egg varieties: A potential risk assessment for human health - Mrityunjoy Biswas; Refat Pervin Annana; Gopal Kumar Kundu; Md Pallob Hossain; AFM Hafizur Rahman; Mahfujul Alam (Food Control, 2025)

Value-added polymer composites using non-metallic industrial waste: A concise review - Gopal Pudhupalayam Muthukutti; Manoj Kumar Singh; Sathish Kumar Palaniappan; Kavimani Vijayananth; Sanjay Mavinkere Rangappa; Suchart Siengchin (Chemical Engineering Journal, 2025)

Molecular virulotyping and advancing the detection of Magnaporthe oryzae using a CRISPR-Cas12a-based diagnostic tool - R. Karan; M. K. Prasannakumar; Harvinder Kour Khera; J. Harish; N. Vamsidharreddy; Gopal Venkateshbabu; Pramesh Devanna; C. Manjunatha; K. B. Palanna; Rakesh Kumar Mishra (World Journal of Microbiology and Biotechnology, 2025)

Antioxidant and anticancer activities of hesperetin and its novel formulations in KB cells - Arunima Chauhan; Salwa; Gayatri Gopal Shedgaonkar; Lalit Kumar; Arka Karmakar; Salil Khajuria; Archana Parampalli Raghavendra; Ruchi Verma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Monitoring slow-moving deep-seated landslide using PSI technique: a case study of a potential sliding slope from southern Taiwan - Abhishek Lakhote; Yu-Chang Chan; Chiao-Yin Lu; Gopal Kumar; Cheng-Wei Sun (Landslides, 2025)
Studying slow-moving, deep-seated landslides is crucial due to their long-lasting effects on landscapes, infrastructure, and communities. In mountainous regions like Taiwan, understanding these landslides is vital for hazard mitigation and land-use planning. Over 2500 pre-existing landslides have been cataloged in Taiwan using LiDAR data, with many identified as potential slow-moving landslide zones, including a significant site, the Liugui-D047, near Hsinfa Village in southern Taiwan. This study aims to understand the E-W and vertical deformation rates at the potential landslide site using the persistent scattering interferometry (PSI) technique. PSI is particularly effective for detecting slow-moving landslides, providing millimeter-level precision in surface deformation measurements over time. By utilizing open-source tools like ISCE and StaMPS, we conducted a five-year PSI analysis from 2018 to 2023 to monitor surface movements at the site. Our results revealed minimal deformation rates, with westward movements ranging from 4.1 to 2.2 mm/yr and vertical downward movements from 4.2 to 1.4 mm/yr. These findings were validated by in situ measurements collected in 2023, confirming the observations of PSI for long-term monitoring. This highlights the effectiveness of combining PSI techniques with open-source tools for monitoring landslide sites, especially in areas with limited in-situ resources. Our study shows that this integration can yield detailed, long-term insights into surface deformations while reducing the costs of extensive in-situ monitoring. Additionally, our findings indicate that the topographically well-defined Liugui-D047 landslide site remained stable with minimal movement over five years, though ongoing monitoring is essential due to multiple influencing factors.

Postharvest Physiology of Mango Crops: Understanding Ripening, Quality, and Storage Strategies - Kuldeep; Ashok Kumar Singh; Mandeep Rawat; Shivam; Gopal Mani; Rakhi Gautam; Rishabh Raj; Imamuddin Shah; Ankit Kumar Pandey; Deepak Maurya; Sampurna Nand Singh; Vinay Kumar (Applied Fruit Science, 2025)

Bhendi yellow vein mosaic virus C4 circumvents the RNA silencing pathway by interacting with SAM synthetase and cystathionine beta synthase - Jeyalakshmi Karanthamalai; Nagesh Srikakulam; Kandhalu Sagadevan Dinesh Babu; Asha Anand; Sachin Mohite; Shantha Kumar; Gopal Pandi (Physiological and Molecular Plant Pathology, 2025)

Conservation tillage-based Arundo donax agro-geotextiles enhance productivity and profitability of sloping croplands in the Indian Himalayas by reducing soil erosion and improving soil organic carbon - Raman Jeet Singh; Gopal Kumar; N.K. Sharma; J.S. Deshwal; Mudit Mishra; Plabani Roy; Ranjan Bhattacharyya; M. Madhu (Journal of Environmental Management, 2025)

Tailoring spinel cobalt-oxide geometry for ultrahigh sensitive nonenzymatic electrocatalytic oxidation and sensing of glucose in batch injection analysis - Yesudas K Yashly; Sathesh P Sreeshma; Saravana Kumar Tharinidevi; Gopal Buvaneswari; Annamalai Senthil Kumar (Chemical Engineering Journal, 2025)

Gold Nanoparticles as a Tool to Detect Biomarkers in Osteoarthritis: New Insights - Atul Mourya; Shristi Arya; Ayush Singh; Gopal Bajad; Soham Loharkar; Shubhra; Pawan Devangan; Neelesh Kumar Mehra; Rahul Shukla; Ramesh Chandra; Jitender Madan (Indian Journal of Microbiology, 2025)

Potential of adaptive co-management in restoring socio-ecological functions of degraded community forests in temperate Himalaya, India - Kottapalli Sreenivasa Rao; Rajeev Lochan Semwal; Ajay Maletha; Sunil Nautiyal; Rakesh Kumar Maikhuri; Krishna Gopal Saxena (Journal of Mountain Science, 2025)

Radiological considerations in using uranium mine waste rock for road construction materials - Gopal P. Verma; Pallavi Singhal; Sanjay Kumar Jha; Pradeep Bhargava; Abhigyan; Vivek Shanker Shrivasatava; Narendra Kumar Shetty; Aditi C. Patra; Dinesh Kumar Aswal (Journal of Environmental Radioactivity, 2025)

Small RNA sequencing analysis provides novel insights into microRNA-mediated regulation of defense responses in chickpea against Fusarium wilt infection - Parichita Priyadarshini; Gopal Kalwan; Deshika Kohli; Deepesh Kumar; C. Bharadwaj; Kishor Gaikwad; Pradeep Kumar Jain (Planta, 2025)

Genomic insights into high-altitude adaptation and evolutionary dynamics of Indian yaks in the Trans-Himalayan region - Karan Mahar; Ankita Gurao; Amod Kumar; Meenakshi Chitkara; Gopal Ramdasji Gowane; Sonika Ahlawat; Saket Kumar Niranjan; Rakesh Kumar Pundir; Reena Arora; Ranjit Singh Kataria; Mahesh Shivanand Dige (Conservation Genetics, 2025)

Predicting temperature variability in major Indian cities using Random Forest Regression (RFR) Model - Ashish Alone; Anoop Kumar Shukla; Gopal Nandan; D R Pattanaik (Journal of Earth System Science, 2025)

CO2 characterization using seismic inversion based on global optimization techniques for enhanced reservoir understanding: a comparative study - Ajay Pratap Singh; Ravi Kant; Satya Prakash Maurya; Brijesh Kumar; Nitin Verma; Raghav Singh; Kumar Hemant Singh; Manoj Kumar Srivastava; Gopal Hema (Acta Geophysica, 2025)

Pleural Fluid Calprotectin Levels in Benign and Malignant Pleural Effusions and Its Significance in Predicting Success of Pleurodesis in Malignant Pleural Effusions - Amartya Chakraborti; Nishant Kumar Chauhan; Naveen Dutt; Mithu Banerjee; Ravisekhar Gadepalli; Deepak Vedant; M. K. Garg; Gopal Durgeshwar; Hariharan Iyer (Indian Journal of Clinical Biochemistry, 2025)

Bycatch and discards of scorpaenoid and dactylopterid fishes from deep-sea shrimp trawlers operating in the southeastern Arabian Sea: Diversity, trophic levels, ecological guilds and towards management priorities - Davood Nihal; K.V. Aneesh Kumar; G.B. Sreekanth; Aiswarya Gopal; M.P. Rajeeshkumar; Hashim Manjebrayakath (Regional Studies in Marine Science, 2025)

Advanced Therapeutic Strategies for Oral Submucous Fibrosis through Stem Cell Therapy - Manoj Kumar Karuppan Perumal; Sava Nanda Gopal; Remya Rajan Renuka; Suresh Kumar Subbiah (Stem Cell Reviews and Reports, 2025)

Socio-ecological Challenges and Adaptation Strategies of Farmers Towards Changing Climate in Vindhyan highlands, India - Sanoj Kumar Patel; Anil Sharma; Anil Barla; Amit Kumar Tiwari; Rinku Singh; Sudhanshu Kumar; Gopal Shankar Singh (Environmental Management, 2025)

Microplastics pollution in Indian marine environment: sources, effects and solutions - Josephine Anthony; Sureka Varalakshmi; Ashok Kumar Sekar; Kumar Thalavai Sivasankarasubbiah; Thilagam Harikrishnan; Vijaya Raghavan Rangamaran; Dharani Gopal; Kirubagaran Ramalingam (Frontiers in Marine Science, 2024)
Microplastic pollution has emerged as a significant environmental challenge globally, posing threats to biodiversity, marine life, and human health. Studies indicate that marine organisms, from plankton to larger fish species, and ultimately humans are ingesting microplastics, leading to physiological harm such as inflammation, digestive blockages, tissue injury, hormonal imbalance, reproductive failure and biomagnification through the food chain. Therefore, there arises an urgent need and demand for implementing effective and sustainable remediation solutions. Though, various mitigation technologies are developed, less information is available on the advantages and disadvantages of the technological advancements. The present review highlights the significant information available on the sources, types, transport of microplastics along with the analytical methods to detect the microplastic pollutions. The global perspective of microplastic pollutions with respect to Indian Marine scenario was highlighted. The recent and advanced mitigation technologies and solutions in preventing, reducing and recycling these microplastic pollutions were also addressed. This review further underscores the need for comprehensive strategies to monitor, manage and mitigate microplastic pollution, including policy interventions, public awareness campaigns, and sustainable waste management practices. Addressing this issue is essential for preserving the health of India’s marine ecosystems and safeguarding the livelihoods of mankind.

Evaluating variability in soil attributes and forest vegetation in a degraded dry tropical region: an ecological restoration perspective - Anil Sharma; Sanoj Kumar Patel; Anil Barla; Gopal Shankar Singh (Environment, Development and Sustainability, 2024)

Unraveling the potential of cyanobacteria as food and investigating its production and nutritional properties - Sreemanti Banerjee; Rupanjali Lahiri; Avik Kumar Choudhury; Anwesha Mondal; Jung-Wan Kim; Davoodbasha MubarakAli; Gour Gopal Satpati (Biocatalysis and Agricultural Biotechnology, 2024)

Size-Fractionated Phytoplankton Biomass in Port Blair Bay, South Andaman Island: Spatial Variability and Environmental Control - Biraja Kumar Sahu; Prasun Goswami; Sanjiba Kumar Baliarsingh; Nambali Valsalan Vinithkumar; Gopal Dharani (Thalassas: An International Journal of Marine Sciences, 2024)

Impact of land use Change on Carbon Management Index- A Study from the Foothills of Western Himalayas - Abhishek Jangir; Sarvendra Kumar; Sushil Kumar Kharia; Pooja Jangra; Prasenjit Ray; N. R. Sudhakara; Mahesh Chand Meena; Gopal Tiwari; Awani Kumar Singh; Gaurav Mishra; Rosa Francaviglia (Journal of Soil Science and Plant Nutrition, 2024)

Climate adaptation in agricultural sector of coastal India: a comprehensive exploration of adaptation strategies - Amitava Panja; Sanchita Garai; Sanjit Maiti; Subhradip Bhattacharjee; Siddhesh Zade; Apoorva Veldandi; Shravani Sahani; Suchandra Dutta; Anil Kumar Reddy; Gopal Sankhala (Mitigation and Adaptation Strategies for Global Change, 2024)

Assessment of metal-associated health risk in different trophic levels in tropical estuary on the southeast coast of India - Vikas Pandey; Dilip Kumar Jha; Ramalingam Kirubagaran; Gopal Dharani (Marine Environmental Research, 2024)

Appraisal of microplastic pollution and its related risks for urban indoor environment in Bangladesh using machine learning and diverse risk evolution indices - Baytune Nahar Netema; Tapos Kumar Chakraborty; Md Simoon Nice; Khandakar Rashedul Islam; Partha Chandra Debnath; Pragga Chowdhury; Md Sozibur Rahman; Monishanker Halder; Samina Zaman; Gopal Chandra Ghosh; Md Shahnul Islam (Environmental Pollution, 2024)

Inland saline culture of GIFT (Oreochromis niloticus) juveniles: effect of graded levels of lipid on growth and haemato-biochemical responses - Vijayakumar Sidramappa Mannur; Naseemashahul Shamna; Parimal Sardar; Narottam Prasad Sahu; Pankaj Kumar; Mritunjoy Paul; Prasanta Jana; Nisha Chuphal; Gopal Krishna (Tropical Animal Health and Production, 2024)

Estimating Soil Organic Carbon Using Sensors Mounted on Unmanned Aircraft System and Machine Learning Algorithms - Rahul Tripathi; Shiv Sundar Jena; Chinmaya Kumar Swain; Gopal Dutta; Bismay Ranjan Tripathy; Sangita Mohanty; P. C. Jena; Asit Pradhan; R. N. Sahoo; S. D. Mohapatra; A. K. Nayak (Journal of the Indian Society of Remote Sensing, 2024)

Soil carbon sequestration potential of different land use systems: evidence from sub-humid southern plains and Aravalli hills of Rajasthan, India - Ram Bhawan Meena; Subhash Chander Meena; Avinash Chandra Rathore; Dinesh Chand Meena; Roshan Lal Meena; Nurnabi Meherul Alam; Kamal Kishor Sharma; Prabhat Kumar; Gopal Lal Meena; Murli Dhar Meena (Environmental Monitoring and Assessment, 2024)

Emerging Research Trends in River Health Assessment: A Bibliometric Analysis - Amit Kumar Tiwari; Rinku Singh; Sanoj Kumar Patel; Sudhanshu Kumar; Nazuk Bhasin; Anil Barla; Gopal Shankar Singh (Anthropocene Science, 2024)

Extreme rainfall storm-induced surface runoff and sediment dynamics of conservation tillage-based agro-geotextiles emplaced on sloping croplands of the Indian Himalayan Region - Raman Jeet Singh; Gopal Kumar; N.K. Sharma; J.S. Deshwal; M. Madhu (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

A sustainable floating dome biogas plants integrated with semi-transparent photovoltaic thermal collectors: Construction, production and economic analysis - Rohit Kumar Singh; Praveen Kumar Srivastava; Gopal Nath Tiwari; Akhoury Sudhir Kumar Sinha (Journal of Cleaner Production, 2024)

Synthesis, delineation and technological advancements of algae biochar for sustainable remediation of the emerging pollutants from wastewater-a review - Gour Gopal Satpati; Anuradha Devi; Debajyoti Kundu; Pritam Kumar Dikshit; Sarveshwaran Saravanabhupathy; Rajlakshmi; Rintu Banerjee; Rajiv Chandra Rajak; Majid Rasool Kamli; Sang-Yul Lee; Jung-Wan Kim; MubarakAli Davoodbasha (Environmental Research, 2024)

Microplastics in the commercially available branded milk in Bangladesh: An emerging threat for human health - Tapos Kumar Chakraborty; MD Jahid Hasan; Baytune Nahar Netema; Md Abu Rayhan; Sk Mahmudul Hasan Asif; Aditi Biswas; Sarajit Sarker; Mahfuz Ahmmed; Md. Simoon Nice; Khandakar Rashedul Islam; Partha Chandra Debnath; Pragga Chowdhury; et al. (Journal of Hazardous Materials, 2024)

First report on molecular and in silico characterization of derma-pharmaceutical potent arbutin from the deep sea halophilic bacteria, Shigella sp. NIOT- DSB91 of Andaman and Nicobar Islands - Lawrance Anburajan; Balakrishnan Meena; Dilip Kumar Jha; Gopal Dharani (Ecological Genetics and Genomics, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Computational identification and experimental validation of potential inhibitors of JAK1 kinase from natural source for the effective treatment of colorectal adenocarcinoma - Prasanna Srinivasan Ramalingam; Gopal Italiya; Sujatha Elangovan; Rudra Awdhesh Kumar Mishra; Mahalakshmi Aranganathan; Eswari Rajangam; Nandhitha Sukumar; Bonny Y Patel; Mekala Janaki Ramaiah; Sangeetha Subramanian; Sivakumar Arumugam (South African Journal of Botany, 2024)

Facile synthesis of silver doped ZnO nanoparticles by thermal decomposition method for photocatalytic degradation of metronidazole under visible light - Dinkar Parashar; Gopal Achari; Mathava Kumar (Journal of Environmental Chemical Engineering, 2024)

Phytoplankton distribution pattern and its implication for the establishment of land-based ballast water treatment technology and test facility in tropical waters - Ponnusamy Sathish Kumar; Krupa Ratnam; Santhanakumar Jeyapal; Dilip Kumar Jha; Vinithkumar Nambali Valsalan; Dharani Gopal; Arthur James Rathinam (Continental Shelf Research, 2024)

Herbicides use in crop production: An analysis of cost-benefit, non-target toxicities and environmental risks - Tapas Kumar Das; Biswaranjan Behera; Chaitanya Prasad Nath; Sourav Ghosh; Suman Sen; Rishi Raj; Sonaka Ghosh; Ajit Ram Sharma; Nanjapur Thimmappagowda Yaduraju; Arpita Nalia; Asik Dutta; Narendra Kumar; et al. (Crop Protection, 2024)

Application of machine learning and multivariate approaches for assessing microplastic pollution and its associated risks in the urban outdoor environment of Bangladesh - Tapos Kumar Chakraborty; Md. Sozibur Rahman; Md. Simoon Nice; Baytune Nahar Netema; Khandakar Rashedul Islam; Partha Chandra Debnath; Pragga Chowdhury; Monishanker Halder; Samina Zaman; Gopal Chandra Ghosh; Md Abu Rayhan; Sk Mahmudul Hasan Asif; et al. (Journal of Hazardous Materials, 2024)

Paradigm of integrative OMICS of microbial technology towards biorefinery prospects - Samuel Jacob; Gunasekaran Rajeswari; Awantika Rai; Sushree Shweta Tripathy; Swathy Gopal; Eeshita Das; Vinod Kumar; S.P. Jeevan Kumar; Tejraj M. Aminabhavi; Vijay Kumar Garlapati (Biocatalysis and Agricultural Biotechnology, 2024)

Unravelling the interaction between Influenza virus and the nuclear pore complex: insights into viral replication and host immune response - Madhu Khanna; Kajal Sharma; Shailendra K. Saxena; Jai Gopal Sharma; Roopali Rajput; Binod Kumar (VirusDisease, 2024)

Selenium Ameliorates Acetaminophen-Induced Oxidative Stress via MAPK and Nrf2 Pathways in Mice - Mylanayakanahosahalli Chandrashekar Indumathi; Kamatam Swetha; Kandahalli Venkataranganayaka Abhilasha; Shiva Siddappa; Shivamadhaiah Manjula Kumar; Govinda Keerthi Prasad; Chu-Huang Chen; Gopal Kedihithlu Marathe (Biological Trace Element Research, 2024)

Implementing 4D seismic inversion based on Linear Programming techniques for CO2 monitoring at the Sleipner field CCS site in the North Sea, Norway - Ajay Pratap Singh; Satya Prakash Maurya; Ravi Kant; Kumar Hemant Singh; Raghav Singh; Manoj Kumar Srivastava; Gopal Hema; Nitin Verma (Acta Geophysica, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

Insights into water absorption characteristics of various waste-based inorganic additives and their application for soil stabilization - Alula Kassa; Ryo Sekine; Thinley Dorji; Gopal Kumar Pathak; Kimitoshi Hayano; Hiromoto Yamauchi; Yoshitoshi Mochizuki (Journal of Cleaner Production, 2024)

Assessing Morphological and Physiological Crop Functional Traits of Underutilized Crops in Response to Different Nutrient Amendments in Vindhyan Highlands, India - Sanoj Kumar Patel; Anil Sharma; Anil Barla; Gopal Shankar Singh (International Journal of Plant Production, 2024)

Virtual screening of acetylcholinesterase inhibitors through pharmacophore-based 3D-QSAR modeling, ADMET, molecular docking, and MD simulation studies - Hitesh Kumar; Ashok Kumar Datusalia; Gopal L. Khatik (In Silico Pharmacology, 2024)

Removing fluoride ions from wastewater by Fe3O4 nanoparticles: Modified Rhodophytes (red algae) as biochar - Amrutashree Hota; S. Gopal Krishna Patro; Sanjaya Kumar Panda; Mohammad Amir Khan; Mohd Abul Hasan; Saiful Islam; Majed Alsubih; Nadeem A. Khan; Sasan Zahmatkesh (Journal of Water Process Engineering, 2024)

Enhanced vermicomposting of rice straw and pressmud with biogas slurry employing Eisenia fetida: Production, characterization, growth, and toxicological risk assessment - Praveen Kumar Srivastava; Gopal Nath Tiwari; Akhoury Sudhir Kumar Sinha (Journal of Environmental Management, 2024)

Salinity, stocking density, and their interactive effects on growth performance and physiological parameters of white-leg shrimp, Penaeus vannamei (Boone, 1931), reared in inland ground saline water - Manmohan Kumar; Narinder Kumar Chadha; Satya Prakash; Annam Pavan-Kumar; Vungarala Harikrishna; P. Gireesh-Babu; Gopal Krishna (Aquaculture International, 2024)

Optimization of weaning age for striped murrel (Channa striata) based on expression and activity of proteases - Rakhi Kumari; P.P. Srivastava; Kedar N. Mohanta; Paramananda Das; Rajesh Kumar; Lakshman Sahoo; Prakash Sharma; Gopal Krishna; Anirban Paul; G.M. Siddaiah (Aquaculture, 2024)

Spatial variation of the broodstock availability of Acanthopagrus berda (Forsskal 1775) with emphasis on seasonality, lunar periodicity, and sex ratio for facilitating efficient breeding program - Suresh Babu Padinhate Purayil; Shilta Madathumpady Thomas; Rajan Kumar; Anuraj Anirudhan; Narayan Dube Praveen; Vaidya Narayan Gopal; Prathibha Rohit; Gopalakrishnan Achamveetil (Regional Studies in Marine Science, 2024)

Performance, Combustion, and Emission analysis of diesel engine fuelled with pyrolysis oil blends and n-propyl alcohol-RSM optimization and ML modelling - K. Sunil Kumar; Raviteja Surakasi; S Gopal Krishna Patro; Nikhil Govil; M.K. Ramis; Abdul Razak; Prabhakar Sharma; Majed Alsubih; Saiful Islam; T.M.Yunus Khan; Naif Almakayeel; Sanjay Chintakindi (Journal of Cleaner Production, 2024)

Microalgae mediated bioremediation of polycyclic aromatic hydrocarbons: Strategies, advancement and regulations - Gour Gopal Satpati; Shalini Gupta; Rohan Kr Biswas; Avik Kumar Choudhury; Jung-Wan Kim; MubarakAli Davoodbasha (Chemosphere, 2023)

Can graphene-based composites and membranes solve current water purification challenges - a comprehensive review - Chetna Tewari; Gaurav Tatrari; Sumit Kumar; Mayank Pathak; Kundan Singh Rawat; Young Nam Kim; Biswajit Saha; Yong Chae Jung; Prithu Mukhopadhyay; Nanda Gopal Sahoo (Desalination, 2023)

Persistence and dissipation kinetics of novaluron 9.45% + lambda-cyhalothrin 1.9% ZC insecticides in tomato crop under semi-arid region - Abdul Rashid Khan Pathan; Bhanwar Lal Jakhar; Shish Ram Dhaka; Mukesh Nitharwal; Hanuman Singh Jatav; Ram Gopal Dudwal; Amit Kumar Yadav; Sandeep Kumar Choudhary; Vishnu Gauttam; Vishnu D. Rajput; Tatiana Minkina (Environmental Geochemistry and Health, 2023)

Antagonistic activity of a novel chitosan-selenium nanoflower against common aquaculture pathogen Aeromonas caviae - Prasad Sowmiya; Tharmathass Stalin Dhas; Dhinakarasamy Inbakandan; Ravi Mani; Anandakumar Natarajan; Gopal Dharani; Kasivelu Govindaraju; Malaichamy Kannan; Karthick Velu; Chirayil Meethalepurayil Vineeth Kumar (Aquaculture International, 2023)

Multi-antibiotics removal under UV-A light using sol-gel prepared TiO2: Central composite design, effect of persulfate addition and degradation pathway study - Dinkar Parashar; Gopal Achari; Mathava Kumar (Chemosphere, 2023)

A Web-Enabled Tool for Site Suitability Mapping for Managed Aquifer Recharge (MAR) Using Google Earth Engine (GEE) and Multi-Criteria Decision Analysis (MCDA) - Nitesh Patidar; Basant Yadav; Sumit Kumar; Abhay Raj; Gopal Krishan; Surjeet Singh; Bhaskar Jyoti Deka; Sanghyun Jeong; Ashish Pandey; Yutaka Matsuno; R. D. Singh (Water Resources Management, 2023)

Distribution and diversity of Fusarium oxysporum f.sp. cubense TR4 causing banana wilt in Sub-tropics of India and comparative analysis of TR4 specific molecular detection methods - Nidhi Kumari; Thukkaram Damodaran; Israr Ahmad; Shailendra Rajan; P. K. Shukla; Muthukumar Manoharan; Amar Kant Kushwaha; Haripal Singh; Ram Gopal; Sangeeta Kumari; Kavita Yadav; Popy Bora; et al. (Journal of Plant Biochemistry and Biotechnology, 2023)

Dietary magnesium chelate alleviates oxidative stress and improves growth in white-leg shrimp, Penaeus vannamei (Boone, 1931), reared in inland saline water - Hougaina Panmei; Prasanta Jana; Tincy Varghese; Paul Nathaniel T; Narinder Kumar Chadha; Gopal Krishna; Gour Hari Pailan; Subrata Dasgupta (Animal Feed Science and Technology, 2023)

Valorization of the insect waste as a source of dietary protein in replacing the fishmeal protein for the cage reared Pangasianodon hypophthalmus: An approach to search the alternate non-conventional feed resource of animal origin - Rahul Das; Basanta Kumar Das; Md. Abul Hassan; Gopal Krishna; Narinder Kumar Chadha; Kiran Dube Rawat; Karmabeer Jena (Animal Feed Science and Technology, 2023)

Role of microbial phytases in improving fish health - Priya; Ishita Virmani; Pragya; Ravi Kumar Goswami; Bijender Singh; Jai Gopal Sharma; Bhoopander Giri (Reviews in Aquaculture, 2023)
Fishmeal is the most preferred protein source in aquafeed industry due to its balanced amino acid and fatty acid profile, but its limited global supply and high price value, necessitates researchers to focus on sustainable alternative sources of protein and plant‐based feed, to meet the growing demand of fish feed. Phytate is a reservoir of phosphorus present in the plants; however, its chelating ability makes it anti‐nutritional. Phytate forms complexes with minerals, proteins, lipids and carbohydrates, confining their accessibility in fish feeds, hence, additional dietary nutrients are required in the fish feed to overcome nutritional deficiencies. The elimination of phytate‐phosphorus through animal faeces and its pass on to aquatic bodies leads to enrichment of nutrients, eutrophication and algal blooms. Microbial phytase segregates phosphorus, minerals, proteins and lower inositol phosphates from phytate. The supplementation of fish feed with microbial phytase enhances the digestibility of minerals, due to which less nutrients are excreted in the faeces; therefore, minimizing pollution in water bodies. Monogastric and agastric animals inherently exhibit the deficiency of phytase; hence, supplementation of dietary material with phytase has been an emerging choice to make dietary nutrients available for fish. Moreover, microbial phytases have a broad pH range and are thermostable, which makes them an excellent choice for commercial fish feed production. Additionally, microbial phytase improves fish growth as these enzymes enhance nutrients bioavailability and their digestion. This review article presents the application of microbial phytases as a feed additive, and their role in enhancing fish growth.

A Bacteriophage-Loaded Microparticle Laden Topical Gel for the Treatment of Multidrug-Resistant Biofilm-Mediated Burn Wound Infection - Deepa Dehari; Aiswarya Chaudhuri; Dulla Naveen Kumar; Meraj Anjum; Rajesh Kumar; Akshay Kumar; Dinesh Kumar; Gopal Nath; Ashish Kumar Agrawal (AAPS PharmSciTech, 2023)

AKR1B1 inhibition using NARI-29-an Epalrestat analogue-alleviates Doxorubicin-induced cardiotoxicity via modulating Calcium/CaMKII/MuRF-1 axis - N.P. Syamprasad; Siddhi Jain; Bishal Rajdev; Samir Ranjan Panda; Jagadeesh Kumar Gangasani; Veerabhadra Swamy Challa; Jayathirtha Rao Vaidya; Gopal C. Kundu; V.G.M. Naidu (Chemico-Biological Interactions, 2023)

Design, synthesis, graph theoretical analysis and molecular modelling studies of novel substituted quinoline analogues as promising anti-breast cancer agents - Prachita Gauns Dessai; Shivani Prabhu Dessai; Renuka Dabholkar; Padmashree Pednekar; Sahili Naik; Shivlingrao Mamledesai; Murugananthan Gopal; Parasuraman Pavadai; Banoth Karan Kumar; Sankaranarayanan Murugesan; Sachin Chandavarkar; Panneerselvam Theivendren; et al. (Molecular Diversity, 2023)

Classifying aerosol type using in situ and satellite observations over a semi-arid station, Anantapur, from southern peninsular India - Suryanarayana Vadde; Raja Obul Reddy Kalluri; Balakrishnaiah Gugamsetty; Rama Gopal Kotalo; Usha Kajjer Virupakshappa; Bhavyasree Akkiraju; Lokeswara Reddy Thotli; Siva Sankara Reddy Lingala; Jeevan Kumar Rapole (Advances in Space Research, 2023)

Assessment of soil vulnerability to erosion in different land surface configurations and management practices under semi-arid monsoon climate - Gopal Kumar; R.S. Kurothe; A.K. Viswakarma; Debashis Mandal; Dipaka Ranjan Sena; Uday Mandal; V.C. Pande; D. Dinesh (Soil and Tillage Research, 2023)

Generation of map on natural environmental background absorbed dose rate in India - Manish K. Mishra; S.K. Jha; Aditi C. Patra; D.G. Mishra; S.K. Sahoo; S.K. Sahu; Gopal P. Verma; Shashank S. Saindane; Pratip Mitra; S. Garg; Vandana Pulhani; I.V. Saradhi; et al. (Journal of Environmental Radioactivity, 2023)

Groundwater Quality Analysis and Drinkability Prediction using Artificial Intelligence - Niranjan Panigrahi; S. Gopal Krishna Patro; Raghvendra Kumar; Michael Omar; Tran Thi Ngan; Nguyen Long Giang; Bui Thi Thu; Nguyen Truong Thang (Earth Science Informatics, 2023)

Exploring the Association Between Statin Use and the Risk of Pancreatic Cancer: an Updated Meta-analysis of Observational Studies - Varunraj Ponnala; Pavan Kumar Narapaka; Pavan Garapati; Gopal Vishwas; Adnan Imam; Sameer Dhingra (Current Pharmacology Reports, 2023)

A state of the art review on the co-cultivation of microalgae-fungi in wastewater for biofuel production - Gour Gopal Satpati; Pritam Kumar Dikshit; Navonil Mal; Ruma Pal; Knawang Chhunji Sherpa; Rajiv Chandra Rajak; Sami-ullah Rather; Sathya Raghunathan; MubarakAli Davoodbasha (Science of The Total Environment, 2023)

Phyto-bacterial biosorption of basic fuchsine: A self-sustainable approach towards biomitigation of contaminant of emerging concern - Neetha Nirupam Jathanna; Girish Kumar Krishnamurthy; Jagdish Gopal Paithankar; Smitha Hegde; Louella Concepta Goveas; Bilachi S. Ravindranath; Mahendra Gowdru (Journal of Environmental Chemical Engineering, 2023)

Occurrences of UV filters, endocrine disruptive chemicals, alkyl phenolic compounds, fragrances, and hormones in the wastewater and coastal waters of the Antarctica - Keshava Balakrishna; Yerabham Praveenkumarreddy; D'Souza Nishitha; Chikmagalur Mallappa Gopal; Jayakrishna Kanhangad Shenoy; Krishnamurthy Bhat; Neloy Khare; Kiran Dhangar; Manish Kumar (Environmental Research, 2023)

Sustainability, productivity, profitability and nutritional diversity of six cropping systems under conservation agriculture: A long term study in eastern India - S.K. Dutta; Alison Laing; Sanjay Kumar; Shweta Shambhavi; Sunil Kumar; Birender Kumar; D.K. Verma; Arun Kumar; Ravi Gopal Singh; Mahesh Gathala (Agricultural Systems, 2023)

Assessment of river channel dynamics and its impact on land use/land cover in the middle Ganga plain, India - Amit Kumar Tiwari; Mallikarjun Mishra; Rinku Singh; Gopal Shankar Singh (Arabian Journal of Geosciences, 2023)

Double transplantation as a climate resilient and sustainable resource management strategy for rice production in eastern Uttar Pradesh, north India - Pradeep Kumar Dubey; Rajan Chaurasia; Krishna Kumar Pandey; Amit Kumar Bundela; Ajeet Singh; Gopal Shankar Singh; Rajesh Kumar Mall; Purushothaman Chirakkuzhyil Abhilash (Journal of Environmental Management, 2023)

An efficient flash flood forecasting system for the un-gaged Meghna basin using open source platform Delft-FEWS - Md. Enayet Chowdhury; AKM Saiful Islam; Matthijs Lemans; Mark Hegnauer; Ashfaqur Rahaman Sajib; Nahruma Mehzabeen Pieu; Mohan Kumar Das; Nur Shadia; Akramul Haque; Binata Roy; Maruf Billah; Faruque Abdullah; et al. (Environmental Modelling & Software, 2023)

PKNNet: a novel feature learning architecture for vegetation mapping using remote sensing hyperspectral image classification - Pradeep Kumar Ladi; Murali Gopal Kakita; Ratnakar Dash; Sandeep Kumar Ladi (Earth Science Informatics, 2023)

Prediction of surface temperature and CO2 emission of leading emitters using grey model EGM (1,1, α, θ) - Pawan Kumar Singh; Alok Kumar Pandey; Anushka Chouhan; Gopal Ji Singh (Environmental Science and Pollution Research, 2023)

Integrated approach for the investigation of groundwater quality through hydrochemistry and water quality index (WQI) - Gopal Krishan; Mohit Kumar; M. Someshwar Rao; Rahul Garg; Brijesh Kumar Yadav; M.L. Kansal; Surjeet Singh; A. Bradley; Marian Muste; L.M. Sharma (Urban Climate, 2023)

Influences of maternal factors on the estimate of genetic parameters for goat feed efficiency traits - Manoj Kumar Singh; Mahesh Shivanand Dige; R. Pourouchottamane; Akhilesh Kumar; Gopal Ramdasji Gowane (Tropical Animal Health and Production, 2022)

Cerium-based metal sulfide derived nanocomposite-embedded rGO as an efficient catalyst for photocatalytic application - Narthana Kandhasamy; Govindhasamy Murugadoss; Thiruppathi Kannappan; Kamalan Kirubaharan; Rajesh Kumar Manavalan; Ramalingam Gopal (Environmental Science and Pollution Research, 2022)

Seasonal variability and its impact on the sub-tidal macrobenthic fauna of Diu Island, north-eastern Arabian Sea: A multivariate approach - Vikas Pandey; Dilip Kumar Jha; Krupa Ratnam; Srinivas Venkatnarayanan; Ponnusamy Sathish Kumar; Pankaj Verma; Gopal Dharani (Frontiers in Marine Science, 2022)

Prolonged Use of Insecticide Dimethoate Inhibits Growth and Photosynthetic Activity of Wheat Seedlings: A Study by Laser-Induced Chlorophyll Fluorescence Spectroscopy - Jitendra Kumar Pandey; Gunjan Dubey; R. Gopal (Journal of Fluorescence, 2022)

Metallic and non-metallic nanoparticles from plant, animal, and fisheries wastes: potential and valorization for application in agriculture - Kishore Kumar Krishnani; Veera Mallu Boddu; Narinder Kumar Chadha; Puja Chakraborty; Jitendra Kumar; Gopal Krishna; Himanshu Pathak (Environmental Science and Pollution Research, 2022)

Unraveling the potential of bacteria isolated from the equatorial region of Indian Ocean in mercury detoxification - Gajendra Joshi; Pankaj Verma; Balakrishnan Meena; Prasun Goswami; D Magesh Peter; Dilip Kumar Jha; Nambali Valsalan Vinithkumar; Gopal Dharani (Frontiers in Marine Science, 2022)
The marine environment is most vital and flexible with continual variations in salinity, temperature, and pressure. As a result, bacteria living in such an environment maintain the adaption mechanisms that are inherent in unstable environmental conditions. The harboring of metal-resistant genes in marine bacteria contributes to their effectiveness in metal remediation relative to their terrestrial counterparts. A total of four mercury-resistant bacteria (MRB) i.e. NIOT-EQR_J7 ( Alcanivorax xenomutans ); NIOT-EQR_J248 and NIOT-EQR_J251 ( Halomonas sp.); and NIOT-EQR_J258 ( Marinobacter hydrocarbonoclasticus ) were isolated from the equatorial region of the Indian Ocean (ERIO) and identified by analyzing the 16S rDNA sequence. The MRBs can reduce up to 70% of Hg(II). The mercuric reductase (merA) gene was amplified and the mercury (Hg) volatilization was confirmed by the X-ray film method. The outcomes obtained from ICP-MS validated that the Halomonas sp. NIOT-EQR_J251 was more proficient in removing the Hg from culture media than other isolates. Fourier transform infrared (FT-IR) spectroscopy results revealed alteration in several functional groups attributing to the Hg tolerance and reduction. The Gas Chromatography-Mass Spectrometry (GC-MS) analysis confirmed that strain Halomonas sp. (NIOT-EQR_J248 and NIOT-EQR_J251) released Isooctyl thioglycolate (IOTG) compound under mercury stress. The molecular docking results suggested that IOTG can efficiently bind with the glutathione S-transferase (GST) enzyme. A pathway has been hypothesized based on the GC-MS metabolic profile and molecular docking results, suggesting that the compound IOTG may mediate mercuric reduction via merA-GST related detoxification pathway.

Comparative evaluation of heavy metal concentration in different organs of the asian seabass: A multivariate approach - Manasi Venkat Koduvayur; Shrivarshini Vasudevan; Vikas Pandey; Jayapal Santhanakumar; Dilip Kumar Jha; Gopal Dharani (Frontiers in Marine Science, 2022)

Impact of Culturable Endophytic Bacteria on Soil Aggregate Formation and Peanut (Arachis hypogaea L.) Growth and Yield Under Drought Conditions - B. Prasanna Kumar; N. Trimurtulu; A. Vijaya Gopal; Y. Nagaraju (Current Microbiology, 2022)

Self-Assembled Maslinic Acid Attenuates Doxorobucin Induced Cytotoxicity via Nrf2 Signaling Pathway: An In Vitro and In Silico Study in Human Healthy Cells - Jhimli Banerjee; Sk Nurul Hasan; Sovan Samanta; Biplab Giri; Braja Gopal Bag; Sandeep Kumar Dash (Cell Biochemistry and Biophysics, 2022)

Evaluating the effect of various environmental factors on the growth of the marine microalgae, Chlorella vulgaris - Anthony Josephine; Thalavai Shivasankarasubbiah Kumar; Baskaran Surendran; Sundaram Rajakumar; Ramalingam Kirubagaran; Gopal Dharani (Frontiers in Marine Science, 2022)

N-glycosylation, a leading role in viral infection and immunity development - Vijay Kant Pandey; Rajani Sharma; Gopal Kumar Prajapati; Tapan Kumar Mohanta; Awdhesh Kumar Mishra (Molecular Biology Reports, 2022)

2-D ionosphere TEC anomaly before January 28, 2020, Cuba earthquake observed from a network of GPS observations data - Gopal Sharma; Rosendo Romero-Andrade; Ajay Kumar Taloor; Gokul Ganeshan; Kamini Kanta Sarma; Shiv Prashad Aggarwal (Arabian Journal of Geosciences, 2022)

Toxicity ameliorative effect of vitamin E against super-paramagnetic iron oxide nanoparticles on haemato-immunological responses, antioxidant capacity, oxidative stress, and metabolic enzymes activity during exposure and recovery in Labeo rohita fingerlings - Munish Kumar; Gyandeep Gupta; Nuzaiba P. Muhammed; Karthik R; Tincy Varghese; Prem Prakash Srivastava; Shashi Bhushan; Satya Prakash Shukla; Gopal Krishna; Subodh Gupta (Aquaculture International, 2022)

Investigation of Coastal Water Characteristics Along the Southeast Coast of India: A Multivariate Approach - Dilip Kumar Jha; Vikas Pandey; Chandrasekaran Muthukumar; Ponnusamy Sathish Kumar; Srinivas Venkatnarayanan; Jebarathnam Prince Prakash Jebakumar; Gopal Dharani (Frontiers in Marine Science, 2022)

63 K and 50 K SNP array based high-density genetic mapping and QTL analysis for productivity and fiber quality traits in cotton - S. Anjan Gowda; Ishwarappa S. Katageri; Rajesh S. Patil; P. Sharat Kumar; Gopal J. Tiwari; Satya N. Jena; Samir V. Sawant (Euphytica, 2022)

Identification and validation of suitable housekeeping genes for gene expression studies in BCR-ABL1 positive B-lineage acute lymphoblastic leukemia - Dikshat Gopal Gupta; Neelam Varma; Ashish Kumar; Shano Naseem; Man Updesh Singh Sachdeva; Parveen Bose; Jogeshwar Binota; Minakshi Gupta; Priti Sonam; Palak Rana; Pankaj Malhotra; Subhash Varma (Molecular Biology Reports, 2022)

Improvement of bacterial blight resistance of the popular variety, Nellore Mahsuri (NLR34449) through marker-assisted breeding - Aleena Dasari; Padma Vemulapalli; Rekha Gonuguntla; Dilip Kumar Thota; Punniakotti Elumalai; Kousik Muppavarapu; Laxmi Prasanna Butam; Swapnil Ravindra Kulkarni; Pragya Sinha; Harika Gunukula; Ravindra Ramarao Kale; Ayyappa Dass Muralidhara; et al. (Journal of Genetics, 2022)

First report of Vanilla distortion mosaic virus on cumin (Cuminum cyminum L.) in India - Ram Dayal Meena; Virendra Kumar Baranwal; Gopal Lal; Yugal Kishor Sharma; Sumer Singh Meena; Narottam Kumar Meena (Journal of Plant Pathology, 2022)

Exosomes as cell-derivative carriers in the diagnosis and treatment of central nervous system diseases - Gayatri Gopal Shetgaonkar; Shirleen Miriam Marques; Cleona E. M. DCruz; R. J. A. Vibhavari; Lalit Kumar; Rupesh Kalidas Shirodkar (Drug Delivery and Translational Research, 2022)
Exosomes are extracellular vesicles with the diameter ranging from 50 to 100 nm and are found in different body fluids such as blood, cerebrospinal fluid (CSF), urine and saliva. Like in case of various diseases, based on the parent cells, the content of exosomes (protein, mRNA, miRNA, DNA, lipids and metabolites) varies and thus can be utilized as potential biomarker for diagnosis and prognosis of the brain diseases. Furthermore, utilizing the natural potential exosomes to cross the blood–brain barrier and by specifically decorating it with the ligand as per the desired brain sites therapeutics can be delivered to brain parenchyma. This review article conveys the importance of exosomes and their use in the treatment and diagnosis of brain/central nervous system diseases. Graphical abstract

The effects of some essential oils on Alternaria alternata, a post-harvest phyto-pathogenic fungus in wheat by disrupting ergosterol biosynthesis - Pachaiyappan Saravana Kumar; Gopal Nattudurai; Villianur Ibrahim Hairul Islam; Savarimuthu Ignacimuthu (Phytoparasitica, 2022)

Evaluation of Physicochemical Characteristics of Coastal Waters of Nellore, Southeast Coast of India, by a Multivariate Statistical Approach - Krupa Ratnam; Dilip Kumar Jha; M. Prashanthi Devi; Gopal Dharani (Frontiers in Marine Science, 2022)
The Swarnamukhi river estuary (SRE), and the surrounding sea in Nellore, southeast coast of India, is one of the least studied marine environments, notably for physicochemical characteristics. Seawater samples were collected from five stations every month from 2014 to 2017 to assess physicochemical characteristics. The open sea (OS) station was significantly different from the inner stations, according to non-metric multidimensional scaling and cluster analysis. The variability was shown by strong factor loadings of atmospheric temperature (0.87), water temperature (0.84), biochemical oxygen demand (0.77), ammonia (0.85), and total nitrogen (0.78). Furthermore, one-way ANOVA and box-whisker plots facilitated simplifying and corroborating multivariate results that showed high concentration in the inner stations. Based on the N/P and Si/N ratios, nitrate and silicate were the key limiting factors in this study. The findings are critical for establishing reference conditions for comparison studies with other comparable ecosystems in the tropical region for better environmental conservation and management.

Valuing Ecosystem Services of Sacred Natural Sites in the Anthropocene: A Case Study of Varanasi, India - Rinku Singh; Amit Kumar Tiwari; Anil Sharma; Sanoj Kumar Patel; Gopal Shankar Singh (Anthropocene Science, 2022)

Inland saline aquaculture increased carbon accumulation rate and stability in pond sediments under semi-arid climate - Vijay Kumar Aralappanavar; Vidya Shree Bharti; Raj Mukhopadhyay; Satya Prakash; Vungarala Harikrishna; Govindarajan Rathi Bhuvaneswari; Gayatri Tripathi; Gopal Krishna; Binoy Sarkar (Journal of Soils and Sediments, 2022)

Soil Properties, Litter Dynamics and Biomass Carbon Storage in Three-Bamboo Species of Sub-Himalayan Region of Eastern India - P. Surath Kumar; Gopal Shukla; Arun Jyoti Nath; Sumit Chakravarty (Water, Air, & Soil Pollution, 2022)

A Mini-Review on Potential of Neuropeptides as Future Therapeutics - Deepika Sharma; Krishan Kumar; Gopal Singh Bisht (International Journal of Peptide Research and Therapeutics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Experimental study of solar energy–based water purifier of single-slope type by incorporating a number of similar evacuated tubular collectors - Sanjeev Kumar Sharma; Ashis Mallick; Desh Bandhu Singh; Gopal Nath Tiwari (Environmental Science and Pollution Research, 2022)

Structural and functional changes in soil bacterial communities by drifting spray application of a commercial red seaweed extract as revealed by metagenomics - Khanjan Trivedi; Ranjeet Kumar; K. G. Vijay Anand; Gopal Bhojani; Denish Kubavat; Arup Ghosh (Archives of Microbiology, 2022)

Traditional knowledge of medicinal plants among three tribal communities of Vindhyan highlands, India: an approach for their conservation and sustainability - Anil Sharma; Sanoj Kumar Patel; Gopal Shankar Singh (Environmental Sustainability, 2021)

Stock structure analysis of the endemic fish, Barbodes carnaticus (Jerdon 1849), for conservation in a biodiversity hotspot - Vijayakumar Leela Ramya; Bijay Kumar Behera; Basanta Kumar Das; Gopal Krishna; Annam Pavankumar; Mujahid Khan Pathan (Environmental Science and Pollution Research, 2021)

Geochemical characterization and regional correlation of Youngest Toba Tuff (YTT, 75 ka) glass shards, Purna alluvial basin, Central India - Ashok Kumar Srivastava; Ajab Singh; Ros Fatihah Binti Haji Muhammad; Jinnappa Pattan; Natwar Sharma; Gopal Parthiban; Neloy Khare (Arabian Journal of Geosciences, 2021)

Distribution and Abundance of Raptors in Kailash Sacred Landscape, Western Himalaya, India - Sumit Kumar Arya; Gopal Singh Rawat; Govindan Veeraswami Gopi (Proceedings of the Zoological Society, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Modelling potentially suitable lac cultivation zones of Butea monosperma to promote livelihood security in rural India - Sharad Tiwari; Brojo Gopal Ghosh; S. N. Vaidya; Sk Mujibar Rahaman; Masjuda Khatun; Sanjoy Garai; Purabi Saikia; Amit Kumar (Vegetos, 2021)

Neutralizing antibody response against subcutaneously injected bacteriophages in rabbit model - Archana Archana; Prem Shankar Patel; Rajesh Kumar; Gopal Nath (VirusDisease, 2021)

Soil loss hinders the restoration potential of tree plantations on highly eroded ravine slopes - Raj Kumar; A. K. Bhardwaj; B. K. Rao; A. K. Vishwakarma; Vijaysinha Kakade; D. Dinesh; Gaurav Singh; Gopal Kumar; V. C. Pande; P. R. Bhatnagar; G. L. Bagdi (Journal of Soils and Sediments, 2021)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Carbon Mineralization and Inorganic Nitrogen Pools under Terminalia chebula Retz.-Based Agroforestry System in Himalayan Foothills, India - Amit Kumar; Gopal Krishna Dwivedi; Salil Tewari; Jai Paul; Rahul Anand; Narendra Kumar; Parmanand Kumar; Hukum Singh; Rajesh Kaushal (Forest Science, 2020)
Soil organic matter is major terrestrial pool for soil organic carbon (C) and nitrogen (N), and their decomposition is sensitive to vegetation and climate change. Integrated nutrient management (INM) deals with the combined application of chemical fertilizers and organic manures for nutritional requirement of crops and avoid the adverse effect of long-term application of chemical fertilizer on crop production and their sustainability. The present study was carried out to investigate the influence of different nutrient sources on soil C mineralization and inorganic N pools in a Terminalia chebula Retz, based on a agroforestry system. The results showed that the highest CO2 evolution was recorded in 100 percent INM and minimum in farmyard manure treatment after 120 days of incubation. Inorganic N was higher under the agroforestry system than under the open system. Among the different nutrient sources, the highest inorganic N was recorded in a 100 percent INM nutrient source and minimal in wheat straw treatment. The yield of turmeric was higher under the T. chebula-based agroforestry system (20.87 t ha–1) than under the open system (19.27 t ha–1). Results suggest that agroforestry systems using the INM approach can enhance C mineralization and inorganic N concentration with improved crop productivity in the Himalayan foothills. Study Implications: Fertilizer has been used since ancient times, and if well managed it can be an asset, promoting sustainable agriculture and increasing crop production, particularly for smallholder farmers in the Himalayan region of India. We compared fertilizer application practices under an agroforestry system in a representative Himalayan region of India. The majority of farmers in the region of the Himalayan foothills having marginal land and they are not able to produce optimum food grains for their requirement. However, their demands are increasing day by day, so to fulfill their demand, they have to adopt agroforestry. Agroforestry may be fulfilling their demand in terms of food, fuel, fodder, and other intangible benefits. Moreover, to increase the production under agroforestry, we have to apply organic and inorganic fertilizer in the soil either as the sole application or as a combination of these fertilizers. The application of these fertilizers will improve the productivity and fertility of land, especially carbon mineralization and inorganic nitrogen. These two soil properties are important to study because these are limiting to land productivity. In addition, efforts to improve integrated nutrient management in the Himalayan region of India would strengthen farmers’ incomes by strengthening land fertility and productivity. The rapid increase in human population over the last century is putting a massive pressure on existing resources, namely soil and water, resulting in environmental degradation in some regions around the world. As productive land becomes scarce, marginalized farmers are pushed into fragile croplands and forest lands unsuitable for modern agriculture which, in turn, is vulnerable, to degradation. If the present trend in population growth persists, pasture and forest lands will be further reduced (Satterthwaite et al. 2010). At this stage, the value of growing trees becomes more significant, and participation in tree planting schemes should be encouraged. However, this option is most feasible when combined with agriculture. As a result, agroforestry is an important management strategy that not only helps to meet the world food requirements but also helps to protect soil from degradation (Ram et al. 2017) and can enhance soil organic matter levels by adding the quantity of above- and below-ground organic matter inputs to soils (Nair et al. 2009, Marone et al. 2017).

Development and characterisation of novel polymorphic microsatellite loci in the freshwater mussel Lamellidens marginalis (Lamarck, 1819) using next generation sequencing - Shubham Varshney; Madhavi Sagwekar; A. Pavan-Kumar; Rekha Das; P. Gireesh-Babu; Aparna Chaudhari; Gopal Krishna (Molluscan Research, 2020)

The potential of arbuscular mycorrhizal fungi in C cycling: a review - Manoj Parihar; Amitava Rakshit; Vijay Singh Meena; Vijai Kumar Gupta; Kiran Rana; Mahipal Choudhary; Gopal Tiwari; Pankaj Kumar Mishra; Arunava Pattanayak; Jaideep Kumar Bisht; Surendra Singh Jatav; Priyanka Khati; et al. (Archives of Microbiology, 2020)

Facile synthesis of chitosan-modified ZnO/ZnFe2O4 nanocomposites for effective remediation of groundwater fluoride - Gautam Kumar Sarma; Raju Sharma; Rosy Saikia; Xavy Borgohain; Saddam Iraqui; Krishna Gopal Bhattacharyya; Md. Harunar Rashid (Environmental Science and Pollution Research, 2020)

Traditional agricultural practices in India: an approach for environmental sustainability and food security - Sanoj Kumar Patel; Anil Sharma; Gopal Shankar Singh (Energy, Ecology and Environment, 2020)

In vitro evaluation to intensify the differential morphogenetic response through plant growth regulators and antibiotic supplementation in sugarcane - Devendra Kumar; Rakesh Singh Sengar; Nisha Malik; Manoj Kumar Yadav; Shalani Gupta; Pooran Chand; Gopal Singh; Pushpendra Kumar (Plant Physiology Reports, 2020)

Earthworms and vermicompost: an eco-friendly approach for repaying nature’s debt - Archana Singh; Natchimuthu Karmegam; Gopal Shankar Singh; Tunira Bhadauria; Soon Woong Chang; Mukesh Kumar Awasthi; Sivasubramaniam Sudhakar; Kantha Deivi Arunachalam; Muniyandi Biruntha; Balasubramani Ravindran (Environmental Geochemistry and Health, 2020)

ANN Model Development for Air Permeability in Biochar Amended Unsaturated Soil - Weiling Cai; Himanshu Kumar; Shan Huang; Sanandam Bordoloi; Ankit Garg; Peng Lin; Phani Gopal (Geotechnical and Geological Engineering, 2020)

Application of Fracture Induced Electromagnetic Radiation (FEMR) technique to detect landslide-prone slip planes - Shreeja Das; Jyotirmoy Mallik; Sandeep Dhankhar; Neeraj Suthar; Amit K. Singh; Vikramjit Dutta; Uttam Gupta; Gopal Kumar; Riya Singh (Natural Hazards, 2020)

Functional annotation and characterization of hypothetical protein involved in blister blight tolerance in tea (Camellia sinensis (L) O. Kuntze) - Gagandeep Singh; Gopal Singh; Romit Seth; Rajni Parmar; Pradeep Singh; Vikram Singh; Sanjay Kumar; Ram Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2019)

Utilization of waste plastic oil in diesel engines: a review - D. Damodharan; B. Rajesh Kumar; K. Gopal; Melvin Victor De Poures; B. Sethuramasamyraja (Reviews in Environmental Science and Bio/Technology, 2019)

Agricultural growth and land use land cover change in peri-urban India - Sanoj Kumar Patel; Pramit Verma; Gopal Shankar Singh (Environmental Monitoring and Assessment, 2019)

Localization, distribution and expression of growth hormone in the brain of Asian Catfish, Clarias batrachus - Raj Naresh Gopal; Pankaj Kumar; Bechan Lal (Brain Structure and Function, 2019)

Seismic behaviour of soft clay and its influence on the response of friction pile foundations - Thejesh Kumar Garala; Gopal S. P. Madabhushi (Bulletin of Earthquake Engineering, 2019)

Delivery of BACE1 siRNA mediated by TARBP-BTP fusion protein reduces β-amyloid deposits in a transgenic mouse model of Alzheimer’s disease - Mohamed Mohamed Haroon; Kamal Saba; Venkata Harshavardhan Boddedda; Jerald Mahesh Kumar; Anant Bahadur Patel; Vijaya Gopal (Journal of Biosciences, 2019)

Development of indices for surface and ground water quality assessment and characterization for Indian conditions - Surjeet Singh; N. C. Ghosh; Gopal Krishan; Sumant Kumar; Suman Gurjar; M. K. Sharma (Environmental Monitoring and Assessment, 2019)

Plant studies in the first Himalayan Biosphere Reserve: a review - Amit Kumar; Mansa Srivastav; Bhupendra S Adhikari; Gopal S Rawat (Journal of Mountain Science, 2019)

An updated checklist of echinoderms of the southeastern Arabian Sea - Usha V. Parameswaran; V. N. Sanjeevan; K. U. Abdul Jaleel; Vinu Jacob; Aiswarya Gopal; Anil Kumar Vijayan; M. Sudhakar (Marine Biodiversity, 2018)

Iron oxide labeling does not affect differentiation potential of human bone marrow mesenchymal stem cells exhibited by their differentiation into cardiac and neuronal cells - Sujata Mohanty; Krishan Gopal Jain; Sushmita Bose Nandy; Anupama Kakkar; Manoj Kumar; Amit Kumar Dinda; Harpal Singh; Alok Ray (Molecular and Cellular Biochemistry, 2018)

Investigation on spatiotemporal distribution of aerosol optical properties over two oceanic regions surrounding Indian subcontinent during summer monsoon season - Chaturvedula Viswanatha Vachaspati; Gurramkonda Reshma Begam; Yadiki Nazeer Ahammed; Kanike Raghavendra Kumar; Tuhin Kumar Mandel; Kotalo Rama Gopal; Rajuru Ramakrishna Reddy (Environmental Science and Pollution Research, 2018)

An efficient method for the sequential production of lipid and carotenoids from the Chlorella Growth Factor-extracted biomass of Chlorella vulgaris - Josephine Anthony; Kumar Thalavai Sivashankarasubbiah; Sreelatha Thonthula; Vijaya Raghavan Rangamaran; Dharani Gopal; Kirubagaran Ramalingam (Journal of Applied Phycology, 2018)

Membrane biofouling by chlorine resistant Bacillus spp.: effect of feedwater chlorination on bacteria and membrane biofouling - Gopal Bhojani; Sweta Binod Kumar; Nirmal Kumar Saha; Soumya Haldar (Biofouling, 2018)

Gene structure and comparative and phylogenetic analyses of Catla catla CYP1A full-length cDNA and its responsiveness to benzo(a)pyrene and copper sulphate at early developmental stages - Kavita Kumari; Gireesh-Babu Pathakota; Shivendra Kumar; Gopal Krishna (Fish Physiology and Biochemistry, 2018)

Economic assessment of agri-horticulture production systems on reclaimed ravine lands in Western India - V. C. Pande; R. S. Kurothe; Gopal Kumar; H. B. Singh; S. P. Tiwari (Agroforestry Systems, 2018)

Index-based assessment of suitability of water quality for irrigation purpose under Indian conditions - Surjeet Singh; N. C. Ghosh; Suman Gurjar; Gopal Krishan; Sumant Kumar; Preeti Berwal (Environmental Monitoring and Assessment, 2018)

Synthesis, antioxidant, and antiviral properties of pyrimidinylsulfamoyl azolyl acetamides - Kuppi Reddy Gari Divya; Donthamsetty V. Sowmya; Suram Durgamma; Vadlamudi Tharanath; Divi Venkataramana Sai Gopal; Malaka Venkateshwarulu Jyothi Kumar; Chippada Appa Rao; Adivireddy Padmaja; Venkatapuram Padmavathi (Medicinal Chemistry Research, 2017)

Fish Scales as Potential Substrate for Production of Alkaline Protease and Amino Acid Rich Aqua Hydrolyzate by Bacillus altitudinis GVC11 - N. Harikrishna; S. Mahalakshmi; K. Kiran Kumar; Gopal Reddy (Indian Journal of Microbiology, 2017)

Hexavalent Chromium Reduction from Pollutant Samples by Achromobacter xylosoxidans SHB 204 and its Kinetics Study - Swapna Tadishetty Hanumanth Rao; Narendra Kumar Papathoti; Ravi Gundeboina; Yahya Khan Mohamed; Gopal Reddy Mudhole; Hameeda Bee (Indian Journal of Microbiology, 2017)

Loss of crop yields in India due to surface ozone: an estimation based on a network of observations - Shyam Lal; Sethuraman Venkataramani; Manish Naja; Jagdish Chandra Kuniyal; Tuhin Kumar Mandal; Pradip Kumar Bhuyan; Kandikonda Maharaj Kumari; Sachchida Nand Tripathi; Ujjaini Sarkar; Trupti Das; Yerramsetti Venkata Swamy; Kotalo Rama Gopal; et al. (Environmental Science and Pollution Research, 2017)

Transcriptomic and proteomic analysis of yellow mosaic diseased soybean - Bapatla Kesava Pavan Kumar; S. Kanakala; V. G. Malathi; P. Gopal; R. Usha (Journal of Plant Biochemistry and Biotechnology, 2017)

Agricultural innovation and adaptation to climate change: empirical evidence from diverse agro-ecologies in South Asia - Gopal Datt Bhatta; Hemant Raj Ojha; Pramod Kumar Aggarwal; V. Rasheed Sulaiman; Parvin Sultana; Dhanej Thapa; Nimisha Mittal; Khemraj Dahal; Paul Thomson; Laxman Ghimire (Environment, Development and Sustainability, 2017)

Lipid Nanocarrier-Mediated Drug Delivery System to Enhance the Oral Bioavailability of Rifabutin - Pradip Nirbhavane; Nalini Vemuri; Neeraj Kumar; Gopal Krishan Khuller (AAPS PharmSciTech, 2017)

Antimicrobial potential and taxonomic investigation of piezotolerant Streptomyces sp. NIOT-Ch-40 isolated from deep-sea sediment - Vishnu Priya Padmanaban; Pankaj Verma; Srividhyalakshmi Venkatabaskaran; Thirupathi Keppayan; Dharani Gopal; Ashok Kumar Sekar; Kirubagaran Ramalingam (World Journal of Microbiology and Biotechnology, 2017)

Is rainfall gradient a factor of livelihood diversification? Empirical evidence from around climatic hotspots in Indo-Gangetic Plains - Gopal Datt Bhatta; Pramod Kumar Aggarwal; Amit Kumar Shrivastava; Lindsay Sproule (Environment, Development and Sustainability, 2016)

Complete mitochondrial genome of threatened mahseer Tor tor (Hamilton 1822) and its phylogenetic relationship within Cyprinidae family - A. PAVAN-KUMAR; SUDHANSHU RAMAN; PRAKASH G. KORINGA; NAMRATA PATEL; TEJAS SHAH; RAJEEV K. SINGH; GOPAL KRISHNA; C. G. JOSHI; P. GIREESH-BABU; APARNA CHAUDHARI (Journal of Genetics, 2016)

Tracing lead contamination in foods in the city of Kolkata, India - Avijit Das; KVSS Krishna; Rajeev Kumar; Anindya Das; Siladitya Sengupta; Joy Gopal Ghosh (Environmental Science and Pollution Research, 2016)

Farmers perception and awareness of climate change: a case study from Kanchandzonga Biosphere Reserve, India - Gopal Shukla; Ashok Kumar; Nazir A. Pala; Sumit Chakravarty (Environment, Development and Sustainability, 2016)

The microspore morphology of some species of Selaginella (Selaginellaceae) from India - Sarvesh Kumar Singh; Nawal Kishor Dubey; Gopal Krishna Srivastava (Palynology, 2016)

Coping with weather adversity and adaptation to climatic variability: a cross-country study of smallholder farmers in South Asia - Gopal Datt Bhatta; Pramod Kumar Aggarwal (Climate and Development, 2016)

On an unusual shallow occurrence of the deep-sea brittle star Ophiomyces delata in the Duncan Passage, Andaman Islands (Northern Indian Ocean) - Usha V. Parameswaran; Abdul Jaleel K. U.; Aiswarya Gopal; Sanjeevan V. N.; Anil Kumar Vijayan (Marine Biodiversity, 2016)

Design, synthesis and mode of action of novel 2-(4-aminophenyl)benzothiazole derivatives bearing semicarbazone and thiosemicarbazone moiety as potent antimicrobial agents - Meenakshi Singh; Sudhir Kumar Singh; Mayank Gangwar; Gopal Nath; Sushil K. Singh (Medicinal Chemistry Research, 2016)

Characterisation and Validation of House Keeping Gene for Expression Analysis in Catla catla (Hamilton) - Kavita Kumari; Gireesh-Babu Pathakota; Pavan-Kumar Annam; Shivendra Kumar; Gopal Krishna (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Genotype–phenotype analysis of von Hippel–Lindau syndrome in fifteen Indian families - Narendranath Vikkath; Sindhu Valiyaveedan; Sheela Nampoothiri; Natasha Radhakrishnan; Gopal S. Pillai; Vasantha Nair; Ginil Kumar Pooleri; Georgie Mathew; Krishnakumar N. Menon; Prasanth S. Ariyannur; Ashok B. Pillai (Familial Cancer, 2015)

Identifying triggers for forest fire and assessing fire susceptibility of forests in Indian western Himalaya using geospatial techniques - Sunil Kumar; Meenakshi; Gopal Das Bairagi; Vandana; Amit Kumar (Natural Hazards, 2015)

Bioefficacy evaluation and dissipation pattern of nanoformulation versus commercial formulation of pyridalyl in tomato (Solanum lycopersicum) - Priya Saini; Madhuban Gopal; Rajesh Kumar; Robin Gogoi; Chitra Srivastava (Environmental Monitoring and Assessment, 2015)

Climatology of ionosphere over low-latitude (Kolkata) using FORMOSAT-3/COSMIC satellite observation - Gopal Mondal; Manojit Gupta; Goutam Kumar Sen (Journal of Earth System Science, 2015)

Residue, dissipation, and safety evaluation of pyridalyl nanoformulation in Okra (Abelmoschus esculentus [L] Moench) - Priya Saini; Madhuban Gopal; Rajesh Kumar; Robin Gogoi (Environmental Monitoring and Assessment, 2015)

Ultraviolet and 5′Fluorodeoxyuridine Induced Random Mutagenesis in Chlorella vulgaris and Its Impact on Fatty Acid Profile: A New Insight on Lipid-Metabolizing Genes and Structural Characterization of Related Proteins - Josephine Anthony; Vijaya Raghavan Rangamaran; Dharani Gopal; Kumar T. Shivasankarasubbiah; Mary Leema J. Thilagam; Magesh Peter Dhassiah; Divya Shridhar M. Padinjattayil; VinithKumar N. Valsalan; Vijayakumaran Manambrakat; Sivakumar Dakshinamurthy; Sivaraman Thirunavukkarasu; Kirubagaran Ramalingam (Marine Biotechnology, 2015)

An acenocoumarol dosing algorithm exploiting clinical and genetic factors in South Indian (Dravidian) population - Dhakchinamoorthi Krishna Kumar; Deepak Gopal Shewade; Marie-Anne Loriot; Philippe Beaune; B. V. Sai Chandran; Jayaraman Balachander; Chandrasekaran Adithan (European Journal of Clinical Pharmacology, 2015)

In vitro antimicrobial activity of o-phenylenediamine-tert-butyl-N-1,2,3-triazole carbamate analogs - Manavendra Kumar Singh; Mayank Gangwar; Dharmendra Kumar; Ragini Tilak; Gopal Nath; Alka Agarwal (Medicinal Chemistry Research, 2014)

Elevation, slope aspect and integrated nutrient management effects on crop productivity and soil quality in North-west Himalayas, India - Birendra Nath Ghosh; Narinder Kumar Sharma; Nurnabi Meherul Alam; Raman Jeet Singh; Gopal Prasad Juyal (Journal of Mountain Science, 2014)

Degradation of Sulphonated Azo Dye Red HE7B by Bacillus sp. and Elucidation of Degradative Pathways - Jyoti Kumar Thakur; Sangeeta Paul; Prem Dureja; K. Annapurna; Jasdeep C. Padaria; Madhuban Gopal (Current Microbiology, 2014)

Mitochondrial ATPase 6/8 genes reveal genetic divergence in the Coilia dussumieri (Valenciennes, 1848) populations of north east and northwest coasts of India - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; P. R. Divya; Raj Kumar; J. K. Jena (Molecular Biology Reports, 2014)

CspA encodes a major cold shock protein in Himalayan psychrotolerant Pseudomonas strains - Shekhar Chandra Bisht; Gopal Kishna Joshi; Pankaj Kumar Mishra (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Comparative morphological studies on spikes of Indian Selaginella Beauv. - Sarvesh Kumar Singh; Brij Bhan Yadav; Manju Srivastava; Pradeep Kumar Shukla; Gopal Krishna Srivastava (Plant Systematics and Evolution, 2014)

Isolation and identification of new phytoconstituents from the fruit extract of Amomum subulatum Roxb. - Gopal Kumar; Baby Chauhan; Mohammed Ali (Natural Product Research, 2014)

Molecular phylogeny of elasmobranchs inferred from mitochondrial and nuclear markers - A. Pavan-Kumar; P. Gireesh-Babu; P. P. Suresh Babu; A. K. Jaiswar; V. Hari Krishna; K. Pani Prasasd; Aparna Chaudhari; S. G. Raje; S. K. Chakraborty; Gopal Krishna; W. S. Lakra (Molecular Biology Reports, 2014)

Effect of CYP2C9, VKORC1, CYP4F2 and GGCX genetic variants on warfarin maintenance dose and explicating a new pharmacogenetic algorithm in South Indian population - Dhakchinamoorthi Krishna Kumar; Deepak Gopal Shewade; Marie-Anne Loriot; Philippe Beaune; Jayaraman Balachander; B. V. Sai Chandran; Chandrasekaran Adithan (European Journal of Clinical Pharmacology, 2014)

Effect of Actin Polymerization Inhibitor During Oocyte Maturation on Parthenogenetic Embryo Development and Ploidy in Capra hircus - R. Ranjan; R. K. Singh; T. Yasotha; Manish Kumar; Gopal Puri; Kuldeep Kumar; Renu Singh; Sanjeev Bhure; D. Malakar; S. K. Bhanja; M. Sarkar; B. C. Das; et al. (Biochemical Genetics, 2013)

Corresponding Properties of Fatty Oils of Cleome viscosa and Jatropha curcas as Resources of Biodiesel - Rashmi Kumari; Gopal Rao Mallavarapu; Vinod Kumar Jain; Sushil Kumar (Agricultural Research, 2013)

Differential responses of system of rice intensification (SRI) and conventional flooded-rice management methods to applications of nitrogen fertilizer - Amod Kumar Thakur; Sreelata Rath; Krishna Gopal Mandal (Plant and Soil, 2013)

Genetic and functional diversity among root-associated psychrotrophic Pseudomonad’s isolated from the Himalayan plants - Shekhar Chandra Bisht; Pankaj Kumar Mishra; Gopal Kishna Joshi (Archives of Microbiology, 2013)

Comparison of Different Approaches to Establish a Core Collection of Andigena (Solanum tuberosum Group Andigena) Potatoes - J. Gopal; Vinod Kumar; Raj Kumar; Prem Mathur (Potato Research, 2013)

Traditional uses of medicinal plants for dermatological healthcare management practices by the Tharu tribal community of Uttar Pradesh, India - Akhilesh Kumar; Vimal Chandra Pandey; Anant Gopal Singh; Divya Darshan Tewari (Genetic Resources and Crop Evolution, 2013)

Mucosal IgA & IL-1β in Helicobacter pylori Infection - Ragini Srivastava; Antara Kashyap; Mohan Kumar; Gopal Nath; Ashok Kumar Jain (Indian Journal of Clinical Biochemistry, 2013)

Ground-based in situ measurements of near-surface aerosol mass concentration over Anantapur: Heterogeneity in source impacts - B. S. K. Reddy; K. R. Kumar; G. Balakrishnaiah; K. R. Gopal; R. R. Reddy; V. Sivakumar; S. Md. Arafath; A. P. Lingaswamy; S. Pavankumari; K. Umadevi; Y. N. Ahammed (Advances in Atmospheric Sciences, 2013)

Effects of cropping on soil properties and organic carbon stock in Deras region, India - Krishna Gopal Mandal; Upasana Baral; Jyotiprakash Padhi; Pradipta Majhi; Hritesh Chakraborty; Ashwani Kumar (Regional Environmental Change, 2012)

Effect of mitotic inducers and retinoic acid blocker on expression of pluripotent genes in ES cells derived from early stage in vitro-produced embryos in buffalo - Ashok Kumar; Kuldeep Kumar; Renu Singh; Gopal Puri; R. Ranjan; T. Yasotha; R. K. Singh; M. Sarkar; Sadhan Bag (In Vitro Cellular & Developmental Biology - Animal, 2012)

Computational approaches to enhance activity of taxanes as antimitotic agent - Ponnurengam Malliappan Sivakumar; Naga Vignesh; Gopal Ramesh Kumar; Mukesh Doble (Medicinal Chemistry Research, 2012)

Inter and intra-ethnic differences in the distribution of the molecular variants of TPMT, UGT1A1 and MDR1 genes in the South Indian population - Gurusamy Umamaheswaran; Dhakchinamoorthi Krishna Kumar; Dhandapani Kayathiri; Subramanian Rajan; Deepak Gopal Shewade; Steven Aibor Dkhar; Sajjanavar Manjunath; Prayaga Ushakiran; Gangadharan Reneega; Kukreti Ritushree; Chandrasekaran Adithan (Molecular Biology Reports, 2012)

Carbon and oxygen isotopic variations in stromatolitic dolomites of Palaeoproterozoic Vempalle Formation, Cuddapah Basin, India - Gopal Chakrabarti; Debasish Shome; Subhasish Kumar; John S. Armstrong-Altrin; Alcides N. Sial (Carbonates and Evaporites, 2011)

Alleviation of cold stress in inoculated wheat (Triticum aestivum L.) seedlings with psychrotolerant Pseudomonads from NW Himalayas - Pankaj Kumar Mishra; Shekhar Chandra Bisht; Pooja Ruwari; Govindan Selvakumar; Gopal Krishna Joshi; Jaideep Kumar Bisht; Jagdish Chandra Bhatt; Hari Shankar Gupta (Archives of Microbiology, 2011)

Laser-Induced Chlorophyll Fluorescence: A Technique for Detection of Dimethoate Effect on Chlorophyll Content and Photosynthetic Activity of Wheat Plant - Jitendra Kumar Pandey; R. Gopal (Journal of Fluorescence, 2011)

Molecular and morphological characterization of somatic hybrids between Solanum tuberosum L. and S. etuberosum Lindl. - Jagesh K. Tiwari; Poonam; D. Sarkar; SK. Pandey; Jai Gopal; S. Raj Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Biological Control of Chickpea Collar Rot by Co-inoculation of Antagonistic Bacteria and Compatible Rhizobia - B. Hameeda; G. Harini; O. P. Rupela; J. V. D. K. Kumar Rao; Gopal Reddy (Indian Journal of Microbiology, 2010)

Peristylus sahanii, a new species of Orchidaceae from India - Pankaj Kumar; Gopal Singh Rawat; Jeewan Singh Jalal (Kew Bulletin, 2010)

Genetic Diversity in Metapenaeus dobsoni using RAPD Analysis - Prem Sagar Mishra; Aparna Chaudhari; Gopal Krishna; Dilip Kumar; W. S. Lakra (Biochemical Genetics, 2009)

Characteristics of spectral aerosol optical depths over India during ICARB - S. Naseema Beegum; K. Krishna Moorthy; Vijayakumar S. Nair; S. Suresh Babu; S. K. Satheesh; V. Vinoj; R. Ramakrishna Reddy; K. Rama Gopal; K. V. S. Badarinath; K. Niranjan; Santosh Kumar Pandey; M. Behera; et al. (Journal of Earth System Science, 2008)

Measurements of surface ozone at semi-arid site Anantapur (14.62°N, 77.65°E, 331 m asl) in India - R. R. Reddy; K. Rama Gopal; L. Siva Sankara Reddy; K. Narasimhulu; K. Raghavendra Kumar; Y. Nazeer Ahammed; C. V. Krishna Reddy (Journal of Atmospheric Chemistry, 2008)

Composition of the essential oil from the root of Artemisia annua - Divya Goel; Richa Goel; Vijender Singh; Mohammed Ali; Gopal Rao Mallavarapu; Sushil Kumar (Journal of Natural Medicines, 2007)

Nitrous oxide emission measurement with acetylene inhibition method in paddy fields under flood conditions - Toshiaki Iida; Sanjit Kumar Deb; Ram Gopal Kharbuja (Paddy and Water Environment, 2007)

Essential oils of petal, leaf and stem of the antimalarial plant Artemisia annua - Divya Goel; Vijender Singh; Mohammed Ali; Gopal Rao Mallavarupu; Sushil Kumar (Journal of Natural Medicines, 2007)

Repeatability of Progeny Mean, Combining Ability, Heterosis and Heterobeltiosis in Early Generations of a Potato Breeding Programme - Raj Kumar; J. Gopal (Potato Research, 2007)

Natural and Anthropogenic Factors Controlling the Dissolved Organic Carbon Concentrations and Fluxes in a Large Tropical River, India - K. Balakrishna; Itta Arun Kumar; G. Srinikethan; Gopal Mugeraya (Environmental Monitoring and Assessment, 2006)

Effect of Carbon Substrates on Rock Phosphate Solubilization by Bacteria from Composts and Macrofauna - B. Hameeda; Y. Harish Kumar Reddy; O.P. Rupela; G.N. Kumar; Gopal Reddy (Current Microbiology, 2006)

Production of Alkaline Lipase by Corynebacterium paurometabolum, MTCC 6841 Isolated from Lake Naukuchiatal, Uttaranchal State, India - Gopal K. Joshi; Sarvesh Kumar; Bhumi Nath Tripathi; Vinay Sharma (Current Microbiology, 2006)

The effectiveness of using a minituber crop for selection of agronomic characters in potato breeding programmes - J. Gopal; Raj Kumar; G. S. Kang (Potato Research, 2002)

The quillworts (Isoetes) of India: distribution, endemism and species radiation - Pradeep Kumar Shukla; Gopal Krishna Srivastava; Santosh Kumar Shukla (Biodiversity and Conservation, 2002)

Impact of Distillery Effluent on Physiological Consequences in the Freshwater Teleost Channa punctatus - S. Kumar; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Deltamethrin Induced Physiological Changes in Freshwater Cat Fish Heteropneustes fossilis - S. Kumar; S. Lata; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 1999)

Suppression of the antibody response to sulfolipids in leprosy patients by 4,4?-diaminodiphenyl sulfone (DDS) - Uma Malik; Gopal K. Khuller; Bhushan Kumar (Antonie van Leeuwenhoek, 1983)